Coating composition and in-mold coating method

By using compounds containing isocyanate reactive groups, polyisocyanate and carbodiimide groups, combined with internal mold release agent, the problems of insufficient water adhesion, hardness and weather resistance of the coating film are solved, and the coating effect with low VOC and high efficiency is achieved.

CN119546715APending Publication Date: 2025-02-28KANSAI PAINT CO LTD

Patent Information

Application Number
CN202380047985.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-22
Filing Date
2023-05-11
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

When forming coating films, the existing coating compositions have insufficient water adhesion, hardness and weather resistance, and the content of volatile organic compounds (VOCs) is high, which affects the environment and energy consumption.

Method used

A compound containing isocyanate reactive groups, a polyisocyanate compound and a carbodiimide group-containing compound are used to form a coating composition with a solid content of more than 90%, and an internal mold release agent is used during the coating process to improve the performance of the coating film.

Benefits of technology

The coating film has high water-adhesiveness, hardness and weather resistance, while significantly reducing the VOC content, improving the environmental friendliness and energy efficiency of the coating process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005257436680000391
    Figure GDA0005257436680000391
  • Figure GDA0005257436680000401
    Figure GDA0005257436680000401
  • Figure GDA0005257436680000451
    Figure GDA0005257436680000451
Patent Text Reader

Abstract

The purpose of the present invention is to provide a coating composition which is capable of forming a coating film having excellent water tightness resistance, hardness, and weather resistance, and which has a low VOC content. The coating composition is characterized by containing (A) a compound containing an isocyanate reactive group, (B) a polyisocyanate compound, and (C) a carbodiimide group-containing compound, and the solid content concentration of the coating composition is 90 mass% or more. In the coating composition, the carbodiimide group-containing compound (C) has an isocyanate group. In the coating composition, the carbodiimide group-containing compound (C) has an aromatic ring structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a coating composition and an in-mold coating method. Background Art

[0002] In the past, in order to give the substrate surface excellent appearance and performance, a coating composition was applied on the substrate surface, and the formed wet coating was cured to form a coating film. In recent years, from the aspect of reducing the environmental burden, it is required to reduce the volatile organic compounds (VOC) in the coating composition and reduce the air conditioning energy during coating.

[0003] And, in recent years, in various technical fields, except the high hardness on the coating surface of base material, also require the high adhesion of coating film and base material, the adhesion (water-resistant adhesion) after the particularly water-resistant load.In addition, when above-mentioned coating composition is applied on the article used outdoors, usually require to form the coating film with high weather resistance.

[0004] Patent document 1 describes a two-component coating material composition, which comprises a coating base component A and a curing component B, characterized in that the coating base component A comprises: i. one or more polyols A1 selected from the group of polyols containing ester groups and having a hydroxyl value of 300 to 500 mgKOH / g and a hydroxyl functionality exceeding 2; ii. a general formula (I) not containing an ether group and an ester group: R 1 -(OH) p (Where R 1 is a p-valent branched, cyclic or linear, saturated or unsaturated aliphatic hydrocarbon radical having 5 to 18 carbon atoms, the radical R 1 One or more aliphatic polyols A2 containing one or more tertiary amino groups (where p is 2 to 6); iii. General formula (II): R 2 -(C=O) r -O-(AO) s -R 3 (Where R 2 is a saturated or unsaturated aliphatic hydrocarbon radical having 6 to 30 carbon atoms, R 3is H, a free radical PO(OH)2, or a free radical of an optionally partially phosphorylated monosaccharide or disaccharide, or a free radical of an optionally partially phosphorylated aldol, AO represents one or more alkylene oxide free radicals selected from the group consisting of ethylene oxide, propylene oxide and butylene oxide, r is 0 or 1, s is 0 to 30) of one or more species A3; iv. one or more crosslinking catalysts A4 selected from the group of organic tin compounds; v. any one or more polyamines A5 having at least 2 secondary amino groups and an amine value of 120 to 280 mgKOH / g; and ix. any one or more additives A9 selected from the group consisting of wetting agents and / or dispersants, rheological aids and flow control agents, and the above-mentioned curing component B contains i. one or more polyisocyanates B1 having an average of 2.4 to 5 NCO groups, in the above-mentioned two-component coating material composition, relative to the total mass of the above-mentioned two-component coating material composition according to ASTM D2369 (2015) contains at least 96% by mass of solid content, and the molar ratio of the NCO group in the above-mentioned curing component B to the acidic hydrogen atoms of the hydroxyl group, primary amino group and secondary amino group in the above-mentioned coating base component A is 1:1.15 to 1:0.95. The two-component coating material composition can be demolded without using an external release agent to avoid damage usually caused by the metal mold surface, and on the other hand, it can ensure extremely excellent adhesion on the substrate, and can be re-coated with further coating films such as primers and clear coats, and can form a surface of extremely excellent quality without the need for expensive and inconvenient cleaning and / or grinding processes.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application No. 2020-528103 Summary of the invention

[0008] Problem that the invention aims to solve

[0009] In the technique described in Patent Document 1, although the VOC content in the obtained coating composition is low, the formed coating film may have insufficient water-resistant adhesion, hardness, and weather resistance.

[0010] An object of the present invention is to provide a coating composition which can form a coating film having excellent water-resistant adhesion, hardness and weather resistance and has a low VOC content.

[0011] Solutions for solving problems

[0012] The present inventors have conducted repeated and intensive studies to achieve the above-mentioned purpose, and as a result, have found that the following coating composition can achieve the above-mentioned purpose, the coating composition being characterized in that it comprises a compound (A) containing an isocyanate-reactive group, a polyisocyanate compound (B) and a compound (C) containing a carbodiimide group, and the solid content concentration of the coating composition is 90% by mass or more.

[0013] That is, the present invention relates to the following <1> ~ <7> .

[0014] <1> A coating composition comprising (A) an isocyanate-reactive group-containing compound, (B) a polyisocyanate compound and (C) a carbodiimide group-containing compound, wherein the coating composition has a solid content concentration of 90% by mass or more.

[0015] <2> like <1> In the coating composition, the carbodiimide group-containing compound (C) has an isocyanate group.

[0016] <3> like <1> or <2> In the coating composition, the carbodiimide group-containing compound (C) has an aromatic ring structure.

[0017] <4> like <1> ~ <3> The coating composition described above, wherein the number average molecular weight of the carbodiimide group-containing compound (C) is within a range of 500 to 5,000.

[0018] <5> An in-mold coating method, comprising the following steps: injecting an in-mold coating composition between a molded substrate and an inner wall of a mold, curing the in-mold coating composition, and then removing the coated molded object from the mold, wherein:

[0019] The above-mentioned in-mold coating composition is <1> ~ <4> The coating composition described in any one of the above.

[0020] <6> like <5> The in-mold coating method, wherein the in-mold coating coating composition further comprises an internal release agent (D).

[0021] <7> like <6> In the in-mold coating method, the internal release agent (D) comprises fatty amide.

[0022] Effects of the Invention

[0023] According to the present invention, it is possible to provide a coating composition which can form a coating film having excellent water-resistant adhesion, hardness and weather resistance and has a low VOC content. DETAILED DESCRIPTION

[0024] Hereinafter, the present invention will be described in detail, but this is merely an example of a preferred embodiment, and the present invention is not limited to these contents.

[0025] [Coating composition]

[0026] The coating composition of the present invention comprises an isocyanate-reactive group-containing compound (A), a polyisocyanate compound (B) and a carbodiimide group-containing compound (C), and the coating composition has a solid content concentration of 90% by mass or more.

[0027] It should be noted that, in this specification, "solid content" refers to non-volatile components such as resin, curing agent, pigment, etc. that remain after drying at 80°C for 30 minutes. The above-mentioned solid content can be obtained by, for example, weighing a sample in a heat-resistant container such as an aluminum foil cup, applying the sample on the bottom of the container and spreading it, drying the sample at 80°C for 30 minutes, and weighing the mass of the components remaining after drying.

[0028] In addition, in this specification, "solid content concentration" refers to the mass ratio of the above-mentioned solid components in the composition. Therefore, the solid content concentration of the composition can be calculated by, for example, measuring 1.0 g of the composition in a heat-resistant container such as an aluminum foil cup, applying the composition on the bottom of the container and spreading it, drying the composition at 80°C for 30 minutes, weighing the mass of the components in the composition remaining after drying, and finding the ratio of the mass of the components remaining after drying to the total mass of the composition before drying.

[0029] The solid content concentration in the coating composition of the present invention is 90% by mass or more. By making the solid content concentration 90% by mass or more, the VOC content in the obtained coating composition can be reduced. From the perspective of the reduction of the VOC content in the obtained coating composition and the anti-blasting property of the formed coating film, the solid content concentration of the coating composition of the present invention is preferably in the range of 95 to 100% by mass, more preferably in the range of 97 to 100% by mass, and further preferably in the range of 99 to 100% by mass.

[0030] [Isocyanate-Reactive Group-Containing Compound (A)]

[0031] The compound (A) containing an isocyanate reactive group is a compound having at least one isocyanate reactive group in one molecule. As the above-mentioned isocyanate reactive group, as long as it is a group reactive to an isocyanate group, there is no particular limitation. As the isocyanate reactive group, for example, a hydroxyl group, an amino group, a thiol group, etc. can be cited. From the aspects of water-resistant adhesion, hardness and weather resistance of the formed coating film, it is preferred to include at least one selected from a hydroxyl group and an amino group, and more preferably a hydroxyl group. Therefore, as the above-mentioned compound (A) containing an isocyanate reactive group, a hydroxyl-containing compound (A1), an amino-containing compound (A2), a thiol-containing compound (A3), etc. can be cited, preferably including at least one compound selected from a hydroxyl-containing compound (A1) and an amino-containing compound (A2), more preferably including a hydroxyl-containing compound (A1).

[0032] [Hydroxy-containing compound (A1)]

[0033] The above-mentioned hydroxyl-containing compound (A1) is a compound having at least one hydroxyl group in one molecule. As the hydroxyl-containing compound (A1), hydroxyl-containing oligomers and hydroxyl-containing polymers can be cited, for example, hydroxyl-containing polyester resins, hydroxyl-containing polycaprolactone resins, hydroxyl-containing polyether resins, hydroxyl-containing polycarbonate resins, hydroxyl-containing acrylic resins, hydroxyl-containing acrylic modified polyester resins, hydroxyl-containing polyurethane resins, hydroxyl-containing epoxy resins, hydroxyl-containing alkyd resins, etc. can be cited. Among them, from the perspective of the reduction of the VOC content in the obtained coating composition, and the water-resistant adhesion, hardness and weather resistance of the formed coating film, it is preferred to include a hydroxyl-containing polyester resin. They can be used alone or in combination of two or more. The above-mentioned hydroxyl-containing polyester resin can usually be manufactured by an esterification reaction or an ester exchange reaction of an acid component and an alcohol component.

[0034] As the acid component, a compound commonly used as a polycarboxylic acid in the production of the hydroxyl-containing polyester resin can be used. Examples of the polycarboxylic acid include aliphatic polybasic acids, alicyclic polybasic acids, and aromatic polybasic acids.

[0035] The above-mentioned aliphatic polybasic acid is generally an aliphatic compound having two or more carboxyl groups in one molecule, an anhydride of the aliphatic compound, and an ester of the aliphatic compound. Examples of the aliphatic polybasic acid include aliphatic polycarboxylic acids such as succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid, octadecanediic acid, citric acid, and butanetetracarboxylic acid; anhydrides of the aliphatic polybasic carboxylic acids; and lower alkyl esters of the aliphatic polybasic carboxylic acids having 1 to 6 carbon atoms, preferably 1 to 4 carbon atoms. The above-mentioned aliphatic polybasic acids can be used alone or in combination of two or more.

[0036] The above-mentioned alicyclic polybasic acid is generally a compound having one or more alicyclic structures and two or more carboxyl groups in one molecule, an anhydride of the compound, and an ester of the compound. The alicyclic structure may be mainly a 4- to 6-membered ring structure. Examples of the alicyclic polybasic acid include alicyclic polybasic carboxylic acids such as 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 4-cyclohexene-1,2-dicarboxylic acid, 3-methyl-1,2-cyclohexanedicarboxylic acid, 4-methyl-1,2-cyclohexanedicarboxylic acid, 1,2,4-cyclohexanetricarboxylic acid, and 1,3,5-cyclohexanetricarboxylic acid; anhydrides of the alicyclic polybasic carboxylic acids; and lower alkyl esters of the alicyclic polybasic carboxylic acids having 1 to 6 carbon atoms, preferably 1 to 4 carbon atoms. The above-mentioned alicyclic polybasic acids may be used alone or in combination of two or more.

[0037] The aromatic polybasic acid is generally an aromatic compound having two or more carboxyl groups in one molecule, an anhydride of the aromatic compound, and an ester of the aromatic compound. Examples of the aromatic polybasic acid include aromatic polybasic carboxylic acids such as phthalic acid, isophthalic acid, terephthalic acid, naphthalene dicarboxylic acid, 4,4'-biphenyl dicarboxylic acid, trimellitic acid, and pyromellitic acid; anhydrides of the aromatic polybasic carboxylic acids; and lower alkyl esters of the aromatic polybasic carboxylic acids having 1 to 6 carbon atoms, preferably 1 to 4 carbon atoms. The aromatic polybasic acids can be used alone or in combination of two or more.

[0038] In addition, acid components other than the above-mentioned aliphatic polybasic acid, alicyclic polybasic acid and aromatic polybasic acid can also be used. As the acid component, there is no particular limitation, for example, fatty acids such as coconut oil fatty acid, cottonseed oil fatty acid, hempseed oil fatty acid, rice bran oil fatty acid, fish oil fatty acid, tall oil fatty acid, soybean oil fatty acid, linseed oil fatty acid, tung oil fatty acid, rapeseed oil fatty acid, castor oil fatty acid, dehydrated castor oil fatty acid, safflower oil fatty acid can be cited; monocarboxylic acids such as isononanoic acid, neodecanoic acid, lauric acid, myristic acid, palmitic acid, stearic acid, oleic acid, linoleic acid, linolenic acid, benzoic acid, p-tert-butylbenzoic acid, cyclohexanoic acid, 10-phenylstearic acid; hydroxycarboxylic acids such as lactic acid, 3-hydroxybutyric acid, 3-hydroxy-4-ethoxybenzoic acid, etc. These acid components can be used alone or in combination of two or more.

[0039] As the alcohol component, a polyol having two or more hydroxyl groups in one molecule can be preferably used. Examples of the polyol include ethylene glycol, propylene glycol, diethylene glycol, trimethylene glycol, tetraethylene glycol, triethylene glycol, dipropylene glycol, 1,4-butanediol, 1,3-butanediol, 2,3-butanediol, 1,2-butanediol, 2-methyl-1,3-propanediol, 3-methyl-1,2-butanediol, 2-butyl-2-ethyl-1,3-propanediol, 1,2-pentanediol, 1,5-pentanediol, 1,4-pentanediol, 2,4-pentanediol, 2,3-dimethyltrimethylene glycol, tetramethylene glycol, 3-methyl-4,3-pentanediol, 3-methyl-1,5-pentanediol, 2,2,4-trimethyl-1,3-pentanediol, 1,6-hexanediol, 1,5-hexanediol, 1,4-hexanediol, 2,5-hexanediol, and neopentyl glycol. , 1,4-cyclohexanedimethanol, tricyclodecane dimethanol, hydroxypivalic acid neopentyl glycol ester, hydrogenated bisphenol A, hydrogenated bisphenol F, dimethylol propionic acid and other diols; polylactone diols formed by adding lactone compounds such as ε-caprolactone to these diols; ester diol compounds such as bis(hydroxyethyl) terephthalate; polyether diol compounds such as alkylene oxide adducts of bisphenol A, polyethylene glycol, polypropylene glycol, polybutylene glycol; trivalent or higher alcohols such as glycerol, trimethylolethane, trimethylolpropane, diglycerol, triglycerol, 1,2,6-hexanetriol, pentaerythritol, dipentaerythritol, tri(2-hydroxyethyl)isocyanuric acid, sorbitol, mannitol; polylactone polyol compounds formed by adding lactone compounds such as ε-caprolactone to these trivalent or higher alcohols; fatty acid esters of glycerol, etc.

[0040] In addition, alcohol components other than the above-mentioned polyols may also be used. The alcohol component is not particularly limited, and examples thereof include monohydric alcohols such as methanol, ethanol, propanol, butanol, isobutanol, amyl alcohol, 2-ethylhexanol, stearyl alcohol, benzyl alcohol, phenylethyl alcohol, and 2-phenoxyethanol; and alcohol compounds obtained by reacting a monoepoxide with an acid, such as propylene oxide, butylene oxide, and "Cardura E10P" (trade name, manufactured by Hexion, a synthetic glycidyl ester of a highly branched saturated fatty acid).

[0041] The method for producing the hydroxyl-containing polyester resin is not particularly limited and can be carried out according to a common method. For example, the hydroxyl-containing polyester resin can be produced by the following method: the acid component and the alcohol component are heated at about 150 to 250° C. for about 5 to 10 hours in a nitrogen gas stream to carry out an esterification reaction or an ester exchange reaction of the acid component and the alcohol component.

[0042] When the acid component and the alcohol component are subjected to an esterification reaction or an ester exchange reaction, these components may be added to the reaction vessel at once, or one or both of them may be added to the reaction vessel in multiple times. Alternatively, the hydroxyl-containing polyester resin may be synthesized first, and then the obtained hydroxyl-containing polyester resin may be reacted with an acid anhydride for half-esterification to produce a carboxyl- and hydroxyl-containing polyester resin. Alternatively, a carboxyl-containing polyester resin may be synthesized, and then the alcohol component may be added to produce the hydroxyl-containing polyester resin.

[0043] As a catalyst for promoting the reaction in the above esterification or transesterification reaction, a known catalyst such as dibutyltin oxide, antimony trioxide, zinc acetate, manganese acetate, cobalt acetate, calcium acetate, lead acetate, tetrabutyl titanate, tetraisopropyl titanate, etc. can be used.

[0044] The hydroxyl-containing polyester resin may be modified with a fatty acid, a monoepoxy compound, a polyisocyanate compound, or the like during or after the production of the resin.

[0045] As the above-mentioned fatty acid, for example, coconut oil fatty acid, cottonseed oil fatty acid, hempseed oil fatty acid, rice bran oil fatty acid, fish oil fatty acid, tall oil fatty acid, soybean oil fatty acid, linseed oil fatty acid, tung oil fatty acid, rapeseed oil fatty acid, castor oil fatty acid, dehydrated castor oil fatty acid, safflower oil fatty acid, etc. can be mentioned. As the above-mentioned monoepoxy compound, for example, "Cardura E10P" (trade name, manufactured by Hexion Co., Ltd., a glycidyl ester of a synthetic highly branched saturated fatty acid) can be preferably used.

[0046] Examples of the polyisocyanate compound include aliphatic diisocyanate compounds such as lysine diisocyanate, hexamethylene diisocyanate, and trimethylhexane diisocyanate; and alicyclic diisocyanates such as hydrogenated xylylene diisocyanate, isophorone diisocyanate, methylcyclohexane-2,4-diisocyanate, methylcyclohexane-2,6-diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), 1,3-(isocyanatomethyl)cyclohexane, and 1,4-(isocyanatomethyl)cyclohexane. Ester compounds; aromatic diisocyanate compounds such as toluene diisocyanate, xylylene diisocyanate, tetramethylxylylene diisocyanate, and diphenylmethane diisocyanate; organic polyisocyanates such as trivalent or higher polyisocyanates such as lysine triisocyanate and 4-(isocyanatomethyl)octamethylene diisocyanate; adducts of these organic polyisocyanates with polyols, low molecular weight polyester resins, water, etc.; cyclized polymers (such as isocyanurates) and biuret-type adducts of these organic polyisocyanates. These polyisocyanate compounds can be used alone or in combination of two or more.

[0047] The hydroxyl value of the hydroxyl-containing polyester resin is preferably within a range of 1 to 600 mgKOH / g, more preferably 100 to 580 mgKOH / g, and even more preferably 300 to 560 mgKOH / g, from the viewpoints of water-resistant adhesion and hardness of the resulting coating film.

[0048] In addition, from the perspectives of reducing the VOC content in the resulting coating composition and improving the water-resistant adhesion of the resulting coating film, the number average molecular weight of the hydroxyl-containing polyester resin is preferably within a range of 200 to 10,000, more preferably within a range of 250 to 5,000, and even more preferably within a range of 300 to 2,500.

[0049] In addition, from the perspective of water-resistant adhesion, hardness and weather resistance of the formed coating film, the glass transition temperature (Tg) of the above-mentioned hydroxyl-containing polyester resin is preferably in the range of -80 to 10°C, more preferably in the range of -70 to 5°C, and further preferably in the range of -60 to 0°C.

[0050] It should be noted that in this specification, the number average molecular weight and the weight average molecular weight are values ​​obtained by converting the retention time (retention capacity) measured using gel permeation chromatography (GPC) into the molecular weight of polystyrene using the retention time (retention capacity) of a standard polystyrene with a known molecular weight measured under the same conditions. Specifically, "HLC-8120GPC" (trade name, manufactured by Tosoh) can be used as a gel permeation chromatography apparatus, "TSKgel G4000HXL", "TSKgel G3000HXL", "TSKgel G2500HXL" and "TSKgel G2000HXL" (trade names, all manufactured by Tosoh) can be used as chromatographic columns, a differential refractometer can be used as a detector, and the measurement can be performed under the conditions of mobile phase: tetrahydrofuran, measurement temperature: 40°C, and flow rate: 1 mL / min.

[0051] The glass transition temperature can be measured, for example, as follows: using a differential scanning calorimeter "DSC-50Q" (manufactured by Shimadzu Corporation, trade name), the sample is placed in a measuring cup, and after vacuum suction to completely remove the solvent, the heat change is measured in the range of -100°C to 150°C at a heating rate of 3°C / min, and the change point of the initial baseline on the low temperature side is taken as the static glass transition temperature.

[0052] When the above-mentioned hydroxyl-containing compound (A1) contains a hydroxyl-containing polyester resin, the content of the hydroxyl-containing polyester resin is preferably in the range of 50 to 100 mass %, more preferably in the range of 60 to 100 mass %, and further preferably in the range of 75 to 100 mass %, based on the total solid content of the hydroxyl-containing compound (A1), from the perspective of water-resistant adhesion and hardness of the formed coating film.

[0053] The hydroxyl-containing polycaprolactone resin can be obtained, for example, by ring-opening polymerization of ε-caprolactone using a divalent to tetravalent polyol as an initiator. Examples of the divalent or higher polyol include ethylene glycol, glycerol, trimethylolethane, trimethylolpropane, diglycerol, ditrimethylolpropane, 1,2,6-hexanetriol, pentaerythritol, tris(2-hydroxyethyl)isocyanuric acid, and polyol compounds obtained by reacting dimethylolalkanoic acid with a monoepoxide (e.g., "Cardura E10P; synthetic glycidyl ester of highly branched saturated fatty acid" manufactured by HEXION Specialty Chemicals). These can be used alone or in combination of two or more.

[0054] In addition, as the above-mentioned hydroxyl-containing polycaprolactone resin, a commercially available product can be used. Examples of commercially available products include "Placcel 205", "Placcel 205H", "Placcel L205AL", "Placcel 205U", "Placcel 208", "Placcel 210", "Placcel 210N", "Placcel 210CP", "Placcel 212", "Placcel L212AL", "Placcel 220", "Placcel 220N", "Placcel 220CPB", "Placcel 220CPT", "Placcel 220UA", "Placcel 220NP1", "Placcel L220AL", "Placcel 220EB", "Placcel 230", "Placcel 230N", "Placcel 240", "Placcel 303", "Placcel 305", "Placcel 308", "Placcel 309", "Placcel 312", "Placcel 320", "Placcel L320AL", "Placcel 410" (these are trade names, manufactured by Daicel Corporation), "TONE 0201", "TONE 0230", "TONE 0249", "TONE 0301", "TONE 0305", "TONE 0310", "TONE 1241", "TONE 1278", "TONE 2221" (these are trade names, manufactured by The Dow Chemical Company), "Capa 2043", "Capa 2101", "Capa 2201", "Capa 2205", "Capa 2209", "Capa 2201A", "Capa 2203A", "Capa 7201A", "Capa 7203", "Capa 3031", "Capa 3050J", "Capa 3091", "Capa 4101" (these are trade names, manufactured by Ingevity Corporation), etc.

[0055] The hydroxyl value of the hydroxyl-containing polycaprolactone resin is preferably within a range of 50 to 900 mgKOH / g, more preferably 100 to 750 mgKOH / g, and even more preferably 130 to 600 mgKOH / g, from the viewpoints of water-resistant adhesion and hardness of the resulting coating film.

[0056] In addition, from the perspective of reducing the VOC content in the resulting coating composition, and the water-resistant adhesion and hardness of the formed coating film, the number average molecular weight of the hydroxyl-containing polycaprolactone resin is preferably in the range of 200 to 5000, more preferably in the range of 250 to 3000, and further preferably in the range of 300 to 2000.

[0057] When the hydroxyl-containing compound (A1) contains a hydroxyl-containing polycaprolactone resin, the content of the hydroxyl-containing polycaprolactone resin is preferably in the range of 5 to 100% by mass, more preferably in the range of 10 to 75% by mass, and even more preferably in the range of 10 to 50% by mass based on the total solid content of the hydroxyl-containing compound (A1), from the perspectives of water-resistant adhesion and hardness of the formed coating film.

[0058] As the above-mentioned hydroxyl-containing polyether resin, the alkylene oxide adducts of the hydroxyl-containing monomers described later, the ring-opening (co)polymers of alkylene oxide or cyclic ethers (tetrahydrofuran, etc.), etc. can be used. Specifically, for example, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, (block or random) copolymers of ethylene glycol-propylene glycol, polyhexamethylene glycol, polyoctamethylene glycol, etc. can be cited. The above-mentioned hydroxyl-containing polyether resins can be used alone or in combination of two or more.

[0059] The hydroxyl value of the hydroxyl-containing polyether resin is preferably within a range of 50 to 600 mgKOH / g, more preferably 70 to 500 mgKOH / g, and even more preferably 90 to 400 mgKOH / g, from the viewpoints of water-resistant adhesion and hardness of the resulting coating film.

[0060] From the perspectives of reducing the VOC content in the resulting coating composition and improving the water-resistant adhesion and hardness of the resulting coating film, the number average molecular weight of the hydroxyl-containing polyether resin is preferably within a range of 200 to 10,000, more preferably within a range of 300 to 5,000, and even more preferably within a range of 400 to 3,000.

[0061] When the hydroxyl-containing compound (A1) contains a hydroxyl-containing polyether resin, the content of the hydroxyl-containing polyether resin is preferably in the range of 5 to 100% by mass, more preferably in the range of 10 to 50% by mass, and even more preferably in the range of 10 to 25% by mass based on the total solid content of the hydroxyl-containing compound (A1), from the perspective of water-resistant adhesion, hardness and weather resistance of the formed coating film.

[0062] The hydroxyl-containing polycarbonate resin is a compound obtained by subjecting a known polyol component to a polycondensation reaction with a carbonylating agent by a conventional method. Examples of the polyol component include diol components and polyol components such as trivalent or higher alcohols.

[0063] Examples of the diol component include linear diols such as 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol; and 2-methyl-1,3-propanediol, 3-methyl-1,5-pentanediol, neopentyl glycol, 2-ethyl-1,6-hexanediol, 2,2-diethyl-1,3-propanediol, 2-butyl-2-ethyl-1,3-propanediol, 2-methyl- Branched diols such as 1,8-octanediol, 2,2,4-trimethyl-1,3-pentanediol, and 2-ethyl-1,3-hexanediol; alicyclic diols such as 1,3-cyclohexanediol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, and 2,2,4,4-tetramethyl-1,3-cyclobutanediol; aromatic diols such as p-xylene glycol and p-tetrachloroxylene glycol; ether diols such as diethylene glycol and dipropylene glycol; polylactone diols obtained by adding lactone compounds such as ε-caprolactone to these diol components, etc. These diol components can be used alone or in combination of two or more.

[0064] Examples of the above-mentioned trivalent or higher alcohols include glycerol, trimethylolethane, trimethylolpropane, trimethylolpropane dimer, pentaerythritol, polylactone polyols obtained by adding lactone compounds such as ε-caprolactone to these trivalent or higher alcohols, etc. These trivalent or higher alcohols can be used alone or in combination of two or more.

[0065] As the carbonylating agent, known substances can be used. Specifically, for example, alkylene carbonate, dialkyl carbonate, diallyl carbonate, phosgene, etc. can be mentioned, and they can be used alone or in combination of two or more. As preferred substances therein, ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, dibutyl carbonate, diphenyl carbonate, etc. can be mentioned.

[0066] The hydroxyl value of the hydroxyl-containing polycarbonate resin is preferably within a range of 50 to 600 mgKOH / g, more preferably 70 to 500 mgKOH / g, and even more preferably 90 to 400 mgKOH / g, from the viewpoints of water-resistant adhesion and hardness of the resulting coating film.

[0067] From the perspectives of reducing the VOC content in the resulting coating composition, and the water-resistant adhesion and hardness of the resulting coating film, the number average molecular weight of the hydroxyl-containing polycarbonate resin is preferably in the range of 200 to 10,000, more preferably in the range of 300 to 5,000, and even more preferably in the range of 400 to 3,000.

[0068] When the above-mentioned hydroxyl-containing compound (A1) contains a hydroxyl-containing polycarbonate resin, the content of the hydroxyl-containing polycarbonate resin is preferably in the range of 5 to 100 mass %, more preferably in the range of 10 to 50 mass %, and further preferably in the range of 10 to 25 mass %, based on the total solid content of the hydroxyl-containing compound (A1), from the perspective of water-resistant adhesion, hardness and weather resistance of the formed coating film.

[0069] The hydroxyl-containing acrylic resin can be produced, for example, by copolymerizing a hydroxyl-containing polymerizable unsaturated monomer and another polymerizable unsaturated monomer copolymerizable with the hydroxyl-containing polymerizable unsaturated monomer by a known method such as solution polymerization in an organic solvent or emulsion polymerization in water.

[0070] The above-mentioned hydroxyl-containing polymerizable unsaturated monomer is a compound having one or more hydroxyl groups and polymerizable unsaturated bonds in one molecule. Examples of the hydroxyl-containing polymerizable unsaturated monomer include monoesters of (meth)acrylic acid and a diol having 2 to 8 carbon atoms, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; ε-caprolactone-modified monoesters of (meth)acrylic acid and a diol having 2 to 8 carbon atoms; N-hydroxymethyl (meth)acrylamide; allyl alcohol, and (meth)acrylates having a polyoxyethylene chain with a hydroxyl group at the molecular end.

[0071] However, in the present invention, the monomers that meet the following (xvii) polymerizable unsaturated monomers having ultraviolet absorbing functional groups should be defined as other polymerizable unsaturated monomers that can copolymerize with the above-mentioned hydroxyl-containing polymerizable unsaturated monomers, excluding the hydroxyl-containing polymerizable unsaturated monomers. They can be used alone or in combination of two or more.

[0072] As other polymerizable unsaturated monomers copolymerizable with the above-mentioned hydroxyl group-containing polymerizable unsaturated monomer, for example, the following monomers (i) to (xx) etc. can be used. These polymerizable unsaturated monomers can be used alone or in combination of two or more.

[0073] (i) Alkyl (meth)acrylate or cycloalkyl (meth)acrylate: for example, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, tridecyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, cyclohexyl (meth)acrylate, methylcyclohexyl (meth)acrylate, tert-butylcyclohexyl (meth)acrylate, cyclododecyl (meth)acrylate, tricyclodecyl (meth)acrylate, etc.

[0074] (ii) Polymerizable unsaturated monomer having an isobornyl group: isobornyl (meth)acrylate, etc.

[0075] (iii) Polymerizable unsaturated compounds having an adamantyl group: adamantyl (meth)acrylate, etc.

[0076] (iv) Polymerizable unsaturated compound having a tricyclodecenyl group: tricyclodecenyl (meth)acrylate, etc.

[0077] (v) Polymerizable unsaturated monomers containing aromatic rings: benzyl (meth)acrylate, styrene, α-methylstyrene, vinyl toluene, etc.

[0078] (vi) Polymerizable unsaturated monomers having an alkoxysilyl group: vinyl trimethoxysilane, vinyl triethoxysilane, vinyl tri(2-methoxyethoxy)silane, γ-(meth)acryloxypropyl trimethoxysilane, γ-(meth)acryloxypropyl triethoxysilane, etc.

[0079] (vii) Polymerizable unsaturated monomers having a fluorinated alkyl group: perfluoroalkyl (meth)acrylates such as perfluorobutyl ethyl (meth)acrylate and perfluorooctyl ethyl (meth)acrylate; fluoroolefins, etc.

[0080] (viii) Polymerizable unsaturated monomers having a photopolymerizable functional group such as a maleimide group

[0081] (ix) Vinyl compounds: N-vinyl pyrrolidone, ethylene, butadiene, chloroprene, vinyl propionate, vinyl acetate, etc.

[0082] (x) Carboxyl-containing polymerizable unsaturated monomers: (meth)acrylic acid, maleic acid, crotonic acid, β-carboxyethyl (meth)acrylate, etc.

[0083] (xi) Nitrogen-containing polymerizable unsaturated monomers: (meth)acrylonitrile, (meth)acrylamide, N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylamide, methylenebis(meth)acrylamide, ethylenebis(meth)acrylamide, adducts of glycidyl (meth)acrylate and amine compounds, etc. (xii) Polymerizable unsaturated monomers having two or more polymerizable unsaturated groups in one molecule: allyl (meth)acrylate, ethylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, etc.

[0084] (xiii) Epoxy-containing polymerizable unsaturated monomers: glycidyl (meth)acrylate, β-methyl glycidyl (meth)acrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, 3,4-epoxycyclohexylethyl (meth)acrylate, 3,4-epoxycyclohexylpropyl (meth)acrylate, allyl glycidyl ether, etc.

[0085] (xiv) (meth)acrylate having a polyoxyethylene chain with an alkoxy group at the molecular end

[0086] (xv) Polymerizable unsaturated monomers having a sulfonic acid group: 2-acrylamide-2-methylpropanesulfonic acid, 2-sulfoethyl (meth)acrylate, allylsulfonic acid, 4-styrenesulfonic acid, etc.; sodium salts and ammonium salts of these sulfonic acids, etc.

[0087] (xvi) Polymerizable unsaturated monomers having a phosphoric acid group: acidic phosphonooxyethyl (meth)acrylate, acidic phosphonooxypropyl (meth)acrylate, acidic phosphonooxypoly (oxyethylene) glycol (meth)acrylate, acidic phosphonooxypoly (oxypropylene) glycol (meth)acrylate, etc.

[0088] (xvii) Polymerizable unsaturated monomers having ultraviolet absorbing functional groups: 2-hydroxy-4-(3-methacryloyloxy-2-hydroxypropoxy)benzophenone, 2-hydroxy-4-(3-acryloyloxy-2-hydroxypropoxy)benzophenone, 2,2'-dihydroxy-4-(3-methacryloyloxy-2-hydroxypropoxy)benzophenone, 2,2'-dihydroxy-4-(3-acryloyloxy-2-hydroxypropoxy)benzophenone, 2-(2'-hydroxy-5'-methacryloyloxyethylphenyl)-2H-benzotriazole, etc.

[0089] (xviii) Light-stable polymerizable unsaturated monomers: 4-(meth)acryloyloxy 1,2,2,6,6-pentamethylpiperidine, 4-(meth)acryloyloxy-2,2,6,6-tetramethylpiperidine, 4-cyano-4-(meth)acryloylamino-2,2,6,6-tetramethylpiperidine, 1-(meth)acryloyl-4-(meth)acryloylamino-2,2,6,6-tetramethylpiperidine, 1-(meth)acryloyl-4-cyano-4-(meth)acryloylamino-2,2,6,6-tetramethylpiperidine, 4-crotonyloxy-2,2,6,6-tetramethylpiperidine, 4-crotonylamino-2,2,6,6-tetramethylpiperidine, 1-crotonyl-4-crotonyloxy-2,2,6,6-tetramethylpiperidine, etc.

[0090] (xix) Polymerizable unsaturated monomers having a carbonyl group: acrolein, diacetone acrylamide, diacetone methacrylamide, acetoacetoxyethyl methacrylate, styrene, vinyl alkyl ketones having 4 to 7 carbon atoms (e.g., vinyl methyl ketone, vinyl ethyl ketone, vinyl butyl ketone), etc.

[0091] (xx) Polymerizable unsaturated monomers having anhydride groups: maleic anhydride, itaconic anhydride, citraconic anhydride, etc.

[0092] In this specification, the polymerizable unsaturated group refers to an unsaturated group that can undergo free radical polymerization. Examples of the polymerizable unsaturated group include vinyl, (meth)acryloyl, (meth)acrylamide, vinyl ether, allyl, propenyl, isopropenyl, and maleimide.

[0093] In addition, in this specification, "(meth)acrylate" means acrylate or methacrylate. "(meth)acrylic acid" means acrylic acid or methacrylic acid. In addition, "(meth)acryloyl" means acryloyl or methacryloyl. In addition, "(meth)acrylamide" means acrylamide or methacrylamide.

[0094] The hydroxyl value of the hydroxyl-containing acrylic resin is preferably within a range of 5 to 240 mgKOH / g, more preferably 20 to 220 mgKOH / g, and even more preferably 25 to 200 mgKOH / g, from the viewpoints of water-resistant adhesion and hardness of the resulting coating film.

[0095] In addition, from the perspectives of reducing the VOC content in the resulting coating composition and improving the water-resistant adhesion of the formed coating film, the weight average molecular weight of the hydroxyl-containing acrylic resin is preferably within a range of 500 to 50,000, more preferably within a range of 1,000 to 30,000, and even more preferably within a range of 1,500 to 10,000.

[0096] In addition, from the perspective of water-resistant adhesion, hardness and weather resistance of the formed coating film, the glass transition temperature (Tg) of the above-mentioned hydroxyl-containing acrylic resin is preferably in the range of -60 to 80°C, more preferably in the range of -50 to 70°C, and further preferably in the range of -40 to 60°C.

[0097] In addition, in this specification, the glass transition temperature (Tg) of the said hydroxyl-containing acrylic resin is the value calculated by the following formula.

[0098] 1 / Tg(K)=W1 / T1+W2 / T2+……Wn / Tn

[0099] Tg(℃)=Tg(K)-273

[0100] Wherein, W1, W2, ... Wn are the mass fractions of the monomers, and T1, T2 ... Tn are the glass transition temperatures Tg (K) of the homopolymers of the monomers.

[0101] It should be noted that the glass transition temperature of the homopolymer of each monomer is based on the value of POLYMER HANDBOOK Fourth Edition, edited by J. Brandrup, Eh Immergut, EA Grulke (1999), and the glass transition temperature of the monomer not recorded in the document is the static glass transition temperature when the homopolymer of the monomer is synthesized in a manner having a weight average molecular weight of about 50,000.

[0102] When the hydroxyl-containing compound (A1) contains a hydroxyl-containing acrylic resin, the content of the hydroxyl-containing acrylic resin is preferably in the range of 5 to 100% by mass, more preferably in the range of 10 to 75% by mass, and even more preferably in the range of 15 to 50% by mass based on the total solid content of the hydroxyl-containing compound (A1), from the perspective of water-resistant adhesion, hardness and weather resistance of the formed coating film.

[0103] Examples of the hydroxyl group-containing compound (A1) include ethylene glycol, propylene glycol, diethylene glycol, trimethylene glycol, tetraethylene glycol, triethylene glycol, dipropylene glycol, 1,4-butanediol, 1,3-butanediol, 2,3-butanediol, 1,2-butanediol, 2-methyl-1,3-propanediol, 3-methyl-1,2-butanediol, 2-butyl-2-ethyl-1,3-propanediol, 1,2-pentanediol, 1,5-pentanediol, 1,4-pentanediol, 2,4-pentanediol, 2,3-dimethyltrimethylene glycol, tetramethylene glycol, 3-methyl-4,3-pentanediol, 3-methyl-1,5-pentanediol, 2,2,4-trimethyl-1,3-pentanediol, 1,6-hexanediol, alcohol, 1,5-hexanediol, 1,4-hexanediol, 2,5-hexanediol, neopentyl glycol, 1,4-cyclohexanedimethanol, tricyclodecane dimethanol, hydroxypivalic acid neopentyl glycol ester, hydrogenated bisphenol A, hydrogenated bisphenol F, glycerol, trimethylolethane, trimethylolpropane, diglycerol, triglycerol, 1,2,6-hexanetriol, pentaerythritol, dipentaerythritol, tris(2-hydroxyethyl)isocyanuric acid, sorbitol, mannitol, hydroxyacetone, 4-(2-hydroxyethyl)morpholine, benzyl alcohol, 2-phenylethanol, 2-phenoxyethanol, naphthalene-1-ol, (1,3-benzofuran-5-yl)methanol, nonylphenol, dinonylphenol, ethoxylated nonylphenol, monostyrenated phenol, distyrenated phenol, tristyrenated phenol, etc. These can be used alone or in combination of two or more.

[0104] When the above-mentioned hydroxyl-containing compound (A1) contains a hydroxyl-containing monomer, the content of the hydroxyl-containing monomer is preferably in the range of 5 to 100 mass %, more preferably in the range of 5 to 50 mass %, and further preferably in the range of 5 to 30 mass %, based on the total solid content of the hydroxyl-containing compound (A1), from the perspective of water-resistant adhesion, hardness and weather resistance of the formed coating film.

[0105] When the above-mentioned isocyanate-reactive group-containing compound (A) contains the above-mentioned hydroxyl-containing compound (A1), the content of the hydroxyl-containing compound (A1) is preferably in the range of 50 to 100 mass %, more preferably in the range of 60 to 100 mass %, and further preferably in the range of 70 to 100 mass %, based on the total solid content of the isocyanate-reactive group-containing compound (A), from the perspective of water-resistant adhesion, hardness and weather resistance of the formed coating film.

[0106] [Amino group-containing compound (A2)]

[0107] The amino group-containing compound (A2) is a compound having at least one primary amino group and / or secondary amino group in the molecule. Examples of the amino group-containing compound (A2) include aliphatic polyamines such as ethylenediamine, pentamethylenediamine, hexamethylenediamine, trimethylhexamethylenediamine, diethylenetriamine, dipropylenetriamine, triethylenetetramine, N,N'-bis-(3-aminopropyl)ethylenediamine, and tetraethylenepentamine; 1,2-cyclohexanediamine, 1,3-cyclohexanediamine, 1,4-cyclohexanediamine, 4-methyl-1,3-cyclohexanediamine, 2-methyl-1,3-cyclohexanediamine, isophoronediamine, 4,4'-methylenebis(cyclohexylamine), 3,3'-dimethyl-4,4'-methylenebis(cyclohexylamine), N,N'-(isopropyl)ethylenediamine, and the like. alicyclic polyamines such as 1,2-bis(aminomethyl)cyclohexane, 1,3-bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, norbornanediamine; heterocyclic polyamines such as piperazine and N-(2-aminoethyl)piperazine; 2,4-toluenediamine, 2,6-toluenediamine, 4,4'-diaminodiphenylmethane, diethyltoluenediamine, dimethylthiotoluenediamine, 4,4'-methylenebis[N-(1-methylpropyl)aniline], 4,4'-diaminodiphenylsulfone, 3,3'-diaminodiphenylsulfone, 4, Aromatic polyamines such as 4'-diaminodiphenyl ether, 1,3-bis(3-aminophenoxy)benzene, 4,4'-(1,3-phenylenediisopropylidene)dianiline, 4,4'-(1,4-phenylenediisopropylidene)dianiline, aminobenzylamine, m-phenylenediamine, p-phenylenediamine, and N,N'-di-sec-butyl-p-phenylenediamine; polyether polyamine compounds such as polyoxypropylene diamine, polyoxyethylene diamine, poly(oxyethylene / oxypropylene) diamine, trimethylolpropane poly(oxypropylene) triamine, and glycerol poly(oxypropylene) triamine; tetraethyl N,N'-(2-methylpentane-1,5-diyl)bisaspartate, N,N'-[methylenebis(cyclohexane-4, Polyaspartic acid ester compounds such as tetraethyl bis(1,4-diethoxy-1,4-dioxobutane-2-yl)amino]propyl}-ω-{2-[(1,4-diethoxy-1,4-dioxobutane-2-yl)amino]propyloxy}poly[oxy(methylethylene)]; aminosilane compounds such as N-β(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β(aminoethyl)-γ-aminopropylmethyldimethoxysilane, and γ-anilinopropyltrimethoxysilane. These compounds can be used alone or in combination of two or more.

[0108] From the perspectives of reducing the VOC content in the resulting coating composition, and the water-resistant adhesion, hardness and weather resistance of the formed coating film, the amino-containing compound (A2) preferably contains at least one compound selected from aliphatic polyamines, alicyclic polyamines, polyether polyamine compounds and polyaspartic acid ester compounds, more preferably contains at least one compound selected from alicyclic polyamines and polyaspartic acid ester compounds, and further preferably contains a polyaspartic acid ester compound.

[0109] As the amino group-containing compound (A2), a commercially available product can be used. Examples of the trade names of commercially available products include “Baxxodur EC110”, “DETA”, “N4 Amine”, “Baxxodur EC210”, “Baxxodur EC201”, “Baxxodur EC330”, “Baxxodur EC331”, “Baxxodur PC136”, “Baxxodur EC130”, “Baxxodur EC280”, “Baxxodur EC301”, “Baxxodur EC302”, “Baxxodur EC303”, “Baxxodur EC310”, and “Baxxodur EC311” (these are trade names, manufactured by BASF), “Clearlink 1000”, “Unilink 4200”, and “Unilink 4100” (these are trade names, manufactured by DORF KETAL), “JEFFAMINE M-600”, “JEFFAMINE M-1000”, “JEFFAMINE M-2005”, “JEFFAMINE M-2070”, and “JEFFAMINE M-3085", "JEFFAMINE D-230", "JEFFAMINE D-400", "JEFFAMINE D-2000", "JEFFAMINE D-4000", "JEFFAMINE ED-600", "JEFFAMINE ED-900", "JEFFAMINE ED-2003", "JEFFAMINE EDR-148", "JEFFAMINERT-1000", "JEFFAMINE T-403", "JEFFAMINE T-3000", "JEFFAMINE T-5000" (these are trade names, manufactured by HUNTSMAN Co., Ltd.), "MXDA", "1,3-BAC" (these are trade names, manufactured by Mitsubishi Gas Chemical Co., Ltd.), "WANAMINE MDA-100H", "ETHACURE 100Plus", "ETHACURE 300", "ETHACURE 420", "Dianiline-M", "Dianiline-P" (these are trade names, manufactured by MITSUI FINE CHEMICALS, INC.), "VESTAMIN IPD", "VESTAMIN TMD", "VESTAMIN PACM", "ANCAMINE 2049", "AMICURE IC-321", "AMICURE IC-322" (these are trade names, manufactured by EVONIK Industries), "DEH20", "DEH.24", "DEH26", "DEH29", "DEH39", "DEH444", "DEH445", "DEH4042", "DEH4044", "DEH487", "DEH488", "DEH530", "DEH" (these are trade names, manufactured by The Dow Chemical Company), "Desmophen NH1220", "Desmophen NH1420", "Desmophen NH1422", "Desmophen NH1423", "Desmophen NH1520", "Desmophen NH1521", "Desmophen NH1523", "Desmophen NH1723LF", "Desmophen NH2885", "Desmophen NH2886" (these are trade names, manufactured by Covestro), "FEISPARTIC F220", "FEISPARTIC F420", "FEISPARTIC F520", "FEISPARTIC F2850", "FEISPARTIC F2872", "FEISPARTIC F221", "FEISPARTIC F321", "FEISPARTIC F525", "FEISPARTIC F421", "FEISPARTIC F524", "FEISPARTIC F330", "FEISPARTIC D2925", "FEISPARTIC D2903" (the above are trade names, made by Feiyang Protech Co., Ltd.), "TSE-EZASP 7980", "TSE-EZASP 7981", "TSE-EZASP 9033", "TSE-EZASP 8443" (the above are trade names, made by TSE Industries Co., Ltd.), "Altor 200", "Altor 201", "Altor 202", "Altor205LV" (the above are trade names, made by Cargill Co., Ltd.), etc.

[0110] As the polyaspartic acid ester compound, a commercially available product can be used. Examples of the trade names of commercially available products include Desmophen NH1220, "Desmophen NH1420," "Desmophen NH1422," "Desmophen NH1423," "Desmophen NH1520," "Desmophen NH1521," "Desmophen NH1523," "Desmophen NH1723LF," "Desmophen NH2885," and "Desmophen NH2886" (these are trade names, manufactured by Covestro), "FEISPARTIC F220," "FEISPARTIC F420," "FEISPARTIC F520," "FEISPARTIC F2850," "FEISPARTIC F2872," "FEISPARTIC F221," "FEISPARTIC F321," "FEISPARTIC F525," "FEISPARTIC F421," "FEISPARTIC F524," "FEISPARTIC F330," and "FEISPARTIC F331." D2925", "FEISPARTIC D2903" (the above are trade names, manufactured by Feiyang Protech Co., Ltd.), "TSE-EZASP 7980", "TSE-EZASP 7981", "TSE-EZASP 9033", "TSE-EZASP 8443" (the above are trade names, manufactured by TSE Industries), "Altor 200", "Altor 201", "Altor 202", "Altor205LV" (the above are trade names, manufactured by Cargill Co., Ltd.), etc.

[0111] When the above-mentioned isocyanate-reactive group-containing compound (A) contains the above-mentioned amino-containing compound (A2), the content of the amino-containing compound (A2) is preferably in the range of 5 to 100 mass %, more preferably in the range of 10 to 80 mass %, and further preferably in the range of 10 to 70 mass %, based on the total solid content of the isocyanate-reactive group-containing compound (A), from the perspective of water-resistant adhesion, hardness and weather resistance of the formed coating film.

[0112] [Thiol group-containing compound (A3)]

[0113] The thiol group-containing compound (A3) is a compound having at least one thiol group in one molecule. Examples of the thiol group-containing compound (A3) include pentaerythritol tetrakis(3-mercaptopropionate), trimethylolpropane tris(3-mercaptopropionate), tris-[(3-mercaptopropionyloxy)-ethyl]-isocyanurate, tetraethylene glycol bis(3-mercaptopropionate), tetramethylene glycol bis(3-mercaptopropionate), dipentaerythritol hexa(3-mercaptopropionate), trimethylolpropane dipropanethiol, pentaerythritol tripropanethiol, pentaerythritol tetrapropanethiol, 1,4-bis(mercaptomethyl)benzene, pentaerythritol tetrakis(3-mercaptobutyrate), trimethylolpropane tris(3-mercaptobutyrate), tetramethylene glycol bis(3-mercaptobutyrate), tris-[(3-mercaptobutyryloxy)-ethyl]-isocyanurate, trimethylolpropane tris(thioglycolate), and pentaerythritol tetrakis(thioglycolate). These can be used alone or in combination of two or more.

[0114] As the thiol group-containing compound (A3), commercially available products can be used. Examples of the trade names of the commercially available products include "TMMP-LV", "TEMPIC", "PEMP-LV", "DPMP", "EGMP-4", "BDMP", "Multhiol Y-2", "Multhiol Y-3", "Multhiol Y-4", and "PXDT" (these are trade names, manufactured by SC Organic Chemical Co., Ltd.), "BDTG", "HDTG", "TMTG", "PETG", "EGTP", "BDTP", "TMTP", and "PETP" (these are trade names, manufactured by Yodo Chemical Co., Ltd.), "Adeka Hardner EH-317" (these are trade names, manufactured by Adeka Co., Ltd.), "Karenz MT PEI", "Karenz MTBDI", "Karenz MT BD1", "Karenz MT TPMB", and "Karenz MT NRI" (these are trade names, manufactured by Showa Denko K.K.), and "jER CURE QX11" and "jER CURE QX40" (these are trade names, manufactured by Mitsubishi Chemical Corporation).

[0115] When the above-mentioned isocyanate-reactive group-containing compound (A) contains the above-mentioned thiol group-containing compound (A3), the content of the thiol group-containing compound (A3) is preferably in the range of 5 to 100 mass %, more preferably in the range of 10 to 50 mass %, and even more preferably in the range of 10 to 30 mass %, based on the total solid content of the isocyanate-reactive group-containing compound (A), from the perspectives of water-resistant adhesion, hardness and weather resistance of the formed coating film.

[0116] The content of the compound (A) containing an isocyanate-reactive group in the coating composition of the present invention is preferably in the range of 15 to 80% by mass, more preferably in the range of 20 to 70% by mass, and further preferably in the range of 25 to 50% by mass, based on the total amount of the coating composition, from the perspective of water-resistant adhesion, hardness and weather resistance of the formed coating film.

[0117] [Polyisocyanate compound (B)]

[0118] The polyisocyanate compound (B) is a compound having at least two isocyanate groups in one molecule, and includes, for example, aliphatic polyisocyanates, alicyclic polyisocyanates, aromatic aliphatic polyisocyanates, aromatic polyisocyanates, and derivatives of these polyisocyanates.

[0119] However, in the present invention, the compound having a carbodiimide group and two or more isocyanate groups is not included in the above-mentioned polyisocyanate compound (B) but is included in the carbodiimide group-containing compound (C).

[0120] Examples of the aliphatic polyisocyanate include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 1,2-butylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, 2,4,4- or 2,2,4-trimethylhexamethylene diisocyanate, dimer acid diisocyanate, 2,6-diisocyanatohexanoic acid methyl ester (common name: lysine diisocyanate), isocyanate); aliphatic diisocyanates such as 2,6-diisocyanatohexanoic acid 2-isocyanatoethyl ester, 1,6-diisocyanato-3-isocyanatomethylhexane, 1,4,8-triisocyanatooctane, 1,6,11-triisocyanatoundecane, 1,8-diisocyanato-4-isocyanatomethyloctane, 1,3,6-triisocyanatohexane, 2,5,7-trimethyl-1,8-diisocyanato-5-isocyanatomethyloctane, etc.

[0121] Examples of the alicyclic polyisocyanate include 1,3-cyclopentene diisocyanate, 1,4-cyclohexane diisocyanate, 1,3-cyclohexane diisocyanate, 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate (common name: isophorone diisocyanate), methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 1,3- or 1,4-cyclohexane diisocyanate. -bis(isocyanatomethyl)cyclohexane (common name: hydrogenated benzyl diisocyanate) or its mixture, alicyclic diisocyanates such as norbornane diisocyanate; 1,3,5-triisocyanatocyclohexane, 1,3,5-trimethylisocyanatocyclohexane, 2-(3-isocyanatopropyl)-2,5-bis(isocyanatomethyl)-bicyclo(2.2.1)heptane, 2-(3-isocyanatopropyl)-2,5-bis(isocyanatomethyl)-bicyclo(2.2.1)heptane, propyl)-2,6-bis(isocyanatomethyl)-bicyclo(2.2.1)heptane, 3-(3-isocyanatopropyl)-2,5-bis(isocyanatomethyl)-bicyclo(2.2.1)heptane, 5-(2-isocyanatoethyl)-2-isocyanatomethyl-3-(3-isocyanatopropyl)-bicyclo(2.2.1)heptane, 6-(2-isocyanatoethyl)-2-isocyanatomethyl alicyclic triisocyanates such as 2-isocyanatomethyl-3-(3-isocyanatopropyl)-bicyclo(2.2.1)heptane, 5-(2-isocyanatoethyl)-2-isocyanatomethyl-2-(3-isocyanatopropyl)-bicyclo(2.2.1)heptane, and 6-(2-isocyanatoethyl)-2-isocyanatomethyl-2-(3-isocyanatopropyl)-bicyclo(2.2.1)heptane.

[0122] Examples of the aromatic aliphatic polyisocyanate include aromatic aliphatic diisocyanates such as 1,3- or 1,4-phenylenediisocyanate or a mixture thereof, ω,ω'-diisocyanato-1,4-diethylbenzene, 1,3- or 1,4-bis(1-isocyanato-1-methylethyl)benzene (common name: tetramethylphenylenediisocyanate) or a mixture thereof; and aromatic aliphatic triisocyanates such as 1,3,5-triisocyanatotoluene.

[0123] Examples of the aromatic polyisocyanate include aromatic diisocyanates such as m-phenylene diisocyanate, p-phenylene diisocyanate, 4,4'-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, 2,4'- or 4,4'-diphenylmethane diisocyanate or a mixture thereof, 2,4- or 2,6-toluene diisocyanate or a mixture thereof, 4,4'-toluidine diisocyanate, and 4,4'-diphenyl ether diisocyanate; aromatic triisocyanates such as triphenylmethane-4,4',4"-triisocyanate, 1,3,5-triisocyanatobenzene, and 2,4,6-triisocyanatotoluene; and aromatic tetraisocyanates such as 4,4'-diphenylmethane-2,2',5,5'-tetraisocyanate.

[0124] Examples of the derivatives of the polyisocyanate compounds include dimers, trimers, biuret, allophanate, uretdione, uretonimine, isocyanurate, iminooxadiazinedione, polymethylene polyphenyl polyisocyanate (crude MDI, polymeric MDI), and crude TDI.

[0125] The above-mentioned polyisocyanates and their derivatives may be used alone or in combination of two or more thereof. Among these polyisocyanates, it is preferred to use aliphatic diisocyanates, aliphatic triisocyanates, alicyclic diisocyanates, aromatic aliphatic diisocyanates and their derivatives alone or in combination of two or more thereof.

[0126] In addition, as the polyisocyanate compound (B), a prepolymer obtained by reacting the polyisocyanate or its derivative with a compound capable of reacting with the polyisocyanate under the condition of excess isocyanate groups can be used. As the compound capable of reacting with the polyisocyanate, for example, compounds having active hydrogen groups such as hydroxyl groups and amino groups can be cited, and specifically, for example, polyols, low molecular weight polyester resins, amines, water, etc. can be used. As the polyol, the polyol used in the description of the hydroxyl-containing polyester resin can be used.

[0127] Regarding the above-mentioned polyisocyanate compound (B), from the perspectives of water-resistant adhesion and hardness of the formed coating film, it is preferably used in a ratio within the range of 0.7 to 2.0 of the isocyanate groups in the polyisocyanate compound (B) relative to the isocyanate-reactive groups in the above-mentioned isocyanate-reactive group-containing compound (A), and more preferably in a ratio within the range of 0.9 to 1.5.

[0128] In addition, the content of the above-mentioned polyisocyanate compound (B) in the coating composition of the present invention is preferably in the range of 10 to 80% by mass, more preferably in the range of 20 to 75% by mass, and further preferably in the range of 30 to 70% by mass, based on the total amount of the coating composition, from the perspective of water-resistant adhesion, hardness and weather resistance of the formed coating film.

[0129] [Carbodiimide group-containing compound (C)]

[0130] The carbodiimide group-containing compound (C) is a compound having at least one carbodiimide group in one molecule, and for example, a compound obtained by subjecting isocyanate groups of an isocyanate group-containing compound to a decarbonation reaction can be used.

[0131] As the carbodiimide group-containing compound, commercial products can be used. As trade names of commercial products, "CARBODILITE V-02B", "CARBODILITE V-05", "Elastostab H01", "CARBODILITE V-03", "CARBODILITE V-07", "CARBODILITE V-09", "CARBODILITE V-09GB", "CARBODILITE V-09M", "CARBODILITE V-04PF" (the above are trade names, manufactured by Nisshinbo Chemical Co., Ltd.), "Stabaxol I", "Stabaxol I LF", "Stabaxol P", "Stabaxol P100", "Stabaxol P200" (the above are trade names, manufactured by LANXESS Co., Ltd.), etc. can be cited.

[0132] Regarding the carbodiimide group-containing compound (C), from the perspectives of reducing the VOC content in the resulting coating composition and the anti-porosity of the formed coating film, it is preferred that the carbodiimide group-containing compound contain a solvent-free compound, and from the perspectives of the water-resistant adhesion of the formed coating film, it is preferred that the compound have an isocyanate group and / or an aromatic ring structure.

[0133] As the solvent-free carbodiimide group-containing compound, a commercial product can be used, and examples of the trade names of the commercial products include "CARBODILITE V-02B", "CARBODILITE V-05", "Elastostab H01", and "CARBODILITE V-04PF" (all manufactured by Nisshinbo Chemical Co., Ltd., trade names).

[0134] When the carbodiimide group-containing compound (C) has an isocyanate group, it preferably has two or more isocyanate groups, and more preferably has two isocyanate groups, from the viewpoint of water-resistant adhesion of the formed coating film and the like.

[0135] As the carbodiimide group-containing compound having an isocyanate group, a commercially available product can be used, and examples of the commercially available product include "CARBODILITE V-05" and "CARBODILITE V-07" (both manufactured by Nisshinbo Chemical Co., Ltd., and trade names).

[0136] In addition, as the carbodiimide group-containing compound having an aromatic ring structure, a commercial product can be used. As the trade names of the commercial products, "CARBODILITE V-05", "Elastostab H01", "CARBODILITE V-04PF", "CARBODILITE V-09M", "CARBODILITE V-09GB" (the above are manufactured by Nisshinbo Chemical Co., Ltd., trade names) and the like can be cited.

[0137] In addition, from the perspective of reducing the VOC content in the resulting coating composition and the water-resistant adhesion of the formed coating film, the number average molecular weight of the above-mentioned carbodiimide group-containing compound (C) is preferably in the range of 500 to 5000, more preferably in the range of 600 to 3000, and further preferably in the range of 700 to 1500.

[0138] In addition, the content of the above-mentioned carbodiimide group-containing compound (C) in the coating composition of the present invention is preferably in the range of 0.5 to 5 mass %, more preferably in the range of 0.8 to 4 mass %, and further preferably in the range of 1.0 to 3 mass %, based on the total amount of the coating composition, from the perspective of water resistance and adhesion of the formed coating film.

[0139] [Internal release agent (D)]

[0140] When the coating composition of the present invention is used as an in-mold coating composition, it is preferred to contain an internal mold release agent (D) from the perspective of the releasability of the formed coating film from the mold. Examples of the internal mold release agent (D) include saturated fatty acids such as stearic acid and palmitic acid; saturated fatty acid salts such as zinc stearate, aluminum stearate, magnesium stearate, calcium stearate, sodium stearate, potassium stearate, barium stearate, zinc palmitate, aluminum palmitate, magnesium palmitate, calcium palmitate, and sodium palmitate; lauramide, myristic amide, palmitamide, stearamide, N,N-dimethyl lauramide, N,N-dimethyl myristic amide, N,N-dimethyl palmitamide, N,N-dimethyl stearyl Saturated fatty acid amides such as amine, N,N-diethyl lauramide, N,N-diethyl myristic amide, N,N-diethyl palmitamide, and N,N-diethyl stearamide; unsaturated fatty acids such as palmitoleic acid and oleic acid; unsaturated fatty acid salts such as zinc palmitoleate, aluminum palmitoleate, magnesium palmitoleate, calcium palmitoleate, sodium palmitoleate, potassium palmitoleate, barium palmitoleate, zinc oleate, aluminum oleate, magnesium oleate, calcium oleate, sodium oleate, potassium oleate, and barium oleate; palmitoleamide, oleamide, erucamide, behenyl unsaturated fatty amides such as amine, N-oleyl palmitamide, N-stearyl erucamide, N,N-dimethyl oleamide, N,N-diethyl oleamide; nonionic surfactants such as polyoxyethylene alkyl ethers and sorbitan alkyl esters; fluorine compounds such as polytetrafluoroethylene, fluoropolyethers, perfluoroalkyl esters and perfluoroalkyl ester salts; phosphate compounds such as monoesters and / or diesters of phosphates having alkyl chains or oxyethylene chains; stearic acid monoglycerides, stearic acid diglycerides, stearic acid triglycerides, stearic acid Fatty acid esters such as sorbitan monoester, stearyl stearate, palmitic acid monoglyceride, palmitic acid diglyceride, palmitic acid triglyceride, behenic acid monoglyceride, behenic acid diglyceride, behenic acid triglyceride, behenic acid behenate, pentaerythritol monostearate, pentaerythritol tetrastearate, pentaerythritol tetrapelargonate, propylene glycol monostearate, stearyl stearate, palmitic acid palmitate, methyl stearate, butyl stearate, methyl laurate, methyl palmitate, isopropyl palmitate, biphenyl biphenate, sorbitan monostearate, and 2-ethylhexyl stearate; soybean oil lecithin, silicone oil, and fatty acid alcohol dibasic acid esters, which can be used alone or in combination of two or more.

[0141] The internal mold release agent (D) preferably contains fatty amide, more preferably contains fatty acid tertiary amide, and further preferably contains fatty acid tertiary dimethyl amide, from the viewpoints of water-resistant adhesion, weather resistance, transparency of the formed coating film, and releasability of the formed coating film from a mold.

[0142] Examples of the fatty amides include saturated fatty amides such as lauramide, myristic amide, palmitamide, stearamide, N,N-dimethyl lauramide, N,N-dimethyl myristic amide, N,N-dimethyl palmitamide, N,N-dimethyl stearamide, N,N-diethyl lauramide, N,N-diethyl myristic amide, N,N-diethyl palmitamide, and N,N-diethyl stearamide; and unsaturated fatty amides such as palmitoleamide, oleamide, erucamide, behenamide, N-oleyl palmitamide, N-stearyl erucamide, N,N-dimethyl oleamide, and N,N-diethyl oleamide.

[0143] As the internal mold release agent containing the above-mentioned fatty acid amide, a commercially available product can be used. Trade names of commercially available products include “INT-120IMC” (these are trade names, manufactured by AXEL PLASTICS), “AMIDE AP-1”, “Diamide Y”, “Diamide O-200”, “Diamide I-200” (these are trade names, manufactured by Mitsubishi Chemical Corporation), “NEUTRON”, “NEUTRON-2”, “NEUTRON-S”, “NEUTRON BNT-22H”, “NEUTRON PNT-34”, “NEUTRON SNT-F” (these are trade names, manufactured by Nippon Seika Co., Ltd.), “ALFLOW S-10”, “ALFLOW E-10”, “ALFLOW P-10” (these are trade names, manufactured by NOF Corporation), “Armoslip CP Powder”, “Armoslip HT Powder”, “Armoslip E” (these are trade names, manufactured by Lion Specialty Chemicals), “FATTY AMIDE S”, “FATTY AMIDE ON”, “FATTY AMIDE E” (these are trade names, manufactured by Kao Corporation), and the like.

[0144] When the internal mold release agent (D) contains the fatty amide, the content of the fatty amide is preferably in the range of 30 to 100 mass %, more preferably in the range of 50 to 100 mass %, and further preferably in the range of 70 to 100 mass %, based on the total amount of the internal mold release agent (D), from the perspectives of water-resistant adhesion and transparency of the formed coating film, and releasability between the formed coating film and the mold.

[0145] As the above-mentioned fatty acid tertiary amide, for example, N, N-dimethyl lauramide, N, N-dimethyl myristic amide, N, N-dimethyl palmitamide, N, N-dimethyl stearamide, N, N-diethyl lauramide, N, N-diethyl myristic amide, N, N-diethyl palmitamide, N, N-diethyl stearamide, N, N-dimethyl oleamide, etc. can be mentioned. As the internal mold release agent comprising the above-mentioned fatty acid tertiary amide, a commercially available product can be used. As the trade name of the commercially available product, " INT-120IMC " (trade name, AXEL PLASTICS company system) etc. can be mentioned.

[0146] When the internal mold release agent (D) contains a tertiary fatty acid amide, the content of the tertiary fatty acid amide is preferably in the range of 20 to 100% by mass, more preferably in the range of 35 to 100% by mass, and even more preferably in the range of 50 to 100% by mass, based on the total amount of the internal mold release agent (D), from the perspectives of water-resistant adhesion and transparency of the formed coating film, and releasability between the formed coating film and the mold.

[0147] As the above-mentioned fatty acid tertiary dimethyl amide, for example, N, N-dimethyl lauramide, N, N-dimethyl myristic amide, N, N-dimethyl palmitamide, N, N-dimethyl stearamide, N, N-dimethyl oleamide, etc. can be mentioned. As the internal mold release agent containing the above-mentioned fatty acid tertiary dimethyl amide, a commercially available product can be used. As the trade name of the commercially available product, "INT-120IMC" (trade name, AXEL PLASTICS company system) etc. can be mentioned.

[0148] When the internal mold release agent (D) contains fatty acid tertiary dimethyl amide, the content of the fatty acid tertiary dimethyl amide is preferably in the range of 20 to 100 mass %, more preferably in the range of 35 to 100 mass %, and further preferably in the range of 50 to 100 mass %, based on the total amount of the internal mold release agent (D), from the perspectives of water-resistant adhesion and transparency of the formed coating film, and releasability between the formed coating film and the mold.

[0149] When the coating composition of the present invention contains the above-mentioned internal mold release agent (D), the content of the internal mold release agent (D) is preferably in the range of 0.4 to 1.5 mass %, more preferably in the range of 0.5 to 1.2 mass %, and even more preferably in the range of 0.5 to 1.0 mass %, based on the total amount of the coating composition, from the perspectives of weather resistance, water-resistant adhesion, transparency of the formed coating film, and releasability between the formed coating film and a mold.

[0150] [Other ingredients]

[0151] In addition to the above-mentioned components, the coating composition of the present invention may also contain an ultraviolet light absorber and / or a light stabilizer. In addition, the coating composition of the present invention may appropriately contain other additives commonly used in the field of coating, such as a crosslinking agent, a solvent (organic solvent, water), a pigment, a catalyst, a dehydrating agent, an antioxidant, a surface conditioner, a defoaming agent, an emulsifier, a surfactant, an antifouling agent, a wetting agent, a thickener, a dye, an abrasion resistance improver, a gloss regulator, etc., as required.

[0152] [Ultraviolet light absorber]

[0153] As the ultraviolet absorber, conventionally known substances can be used, for example, benzotriazole absorbers, triazine absorbers, salicylic acid derivative absorbers, benzophenone absorbers, etc. The ultraviolet absorber may have a polymerizable unsaturated group.

[0154] Specific examples of the benzotriazole absorbent include 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-5'-tert-butylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)benzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)benzotriazole, -5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-tert-amylphenyl)benzotriazole, 2-(2'-hydroxy-4'-octyloxyphenyl)benzotriazole, 2-{2'-hydroxy-3'-(3",4",5",6"-tetrahydrophthalimidomethyl)-5'-methylphenyl}benzotriazole, 2-[2-hydroxy-5-[2-(methacryloyloxy)ethyl]phenyl]-2H-benzotriazole, etc.

[0155] Specific examples of the above-mentioned triazine absorbents include 2,4-bis(2,4-dimethylphenyl)-6-(2-hydroxy-4-isooctyloxyphenyl)-1,3,5-triazine, 2-[4((2-hydroxy-3-dodecyloxypropyl)-oxy)-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, 2-[4-((2-hydroxy-3-tridecyloxypropyl)-oxy)-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, and 2-(2,4-dihydroxyphenyl)-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine.

[0156] Specific examples of the salicylic acid derivative absorbent include phenyl salicylate, p-octylphenyl salicylate, 4-tert-butylphenyl salicylate, and the like.

[0157] Specific examples of the benzophenone absorbent include 4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2,2'-dihydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxy-2'-carboxybenzophenone, 2-hydroxy-4-methoxy-5-sulfobenzophenone trihydrate, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2-hydroxy-4-octyloxybenzophenone, 2-hydroxy-4-octadecyloxybenzophenone, Ketone, sodium 2,2'-dihydroxy-4,4'-dimethoxy-5-sulfobenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 4-dodecyloxy-2-hydroxybenzophenone, 5-chloro-2-hydroxybenzophenone, resorcinol monobenzoate, 2,4-dibenzoylresorcinol, 4,6-dibenzoylresorcinol, hydroxydodecylbenzophenone, 2,2'-dihydroxy-4 (3-methacryloyloxy-2-hydroxypropoxy)benzophenone, etc.

[0158] In addition, commercially available products of the above-mentioned ultraviolet absorbers include, for example, "TINUVIN 1130", "TINUVIN 900", "TINUVIN 928", "TINUVIN 384-2", "TINUVIN 479", "TINUVIN 477", "TINUVIN 405", "TINUVIN 400" (trade names manufactured by BASF, TINUVIN is a registered trademark), "RUVA 93" (trade name manufactured by Otsuka Chemical Co., Ltd.), etc.

[0159] When the coating composition of the present invention contains the above-mentioned ultraviolet absorber, the content of the ultraviolet absorber is preferably in the range of 0.5 to 10 mass %, more preferably in the range of 0.8 to 5.0 mass %, and even more preferably in the range of 1.0 to 3.0 mass %, based on the total amount of the coating composition, from the perspective of weather resistance of the formed coating film, etc.

[0160] [Light stabilizer]

[0161] The light stabilizer is used as a radical chain inhibitor for capturing active radical species generated in the deterioration process of the coating film, and examples thereof include light stabilizers of hindered amine compounds.

[0162] Examples of the hindered amine compound include bis(1,2,2,6,6-pentamethyl-4-piperidyl) sebacate, bis(2,2,6,6-tetramethyl-4-piperidyl) sebacate, bis(N-methyl-2,2,6,6-tetramethyl-4-piperidyl) sebacate, 4-benzoyloxy-2,2',6,6'-tetramethylpiperidine, bis(1,2,2,6,6-pentamethyl-4-piperidyl){[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]- Monomer-type substances such as [(2,2,6,6-tetramethyl-4-piperidinyl)imino]hexamethylene[(2,2,6,6-tetramethyl-4-piperidinyl)imino]} and oligomer-type substances; polyester-bonded substances such as a polyester of 4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol and succinic acid, etc., but are not limited thereto. As the light stabilizer, a known polymeric light stabilizer can also be used.

[0163] Examples of commercially available products of the light stabilizer include "TINUVIN 123", "TINUVIN 152", "TINUVIN 249", "TINUVIN 292" (manufactured by BASF, trade names, TINUVIN is a registered trademark), "HOSTAVIN 3058" (manufactured by Clariant, trade name, Hostavin is a registered trademark), and "ADK STAB LA-82" (manufactured by ADEKA Co., Ltd., trade name, ADK STAB is a registered trademark).

[0164] When the coating composition of the present invention contains the above-mentioned light stabilizer, the content of the light stabilizer is preferably in the range of 0.5 to 10% by mass, more preferably in the range of 0.8 to 7.5% by mass, and even more preferably in the range of 1.0 to 5.0% by mass based on the total amount of the coating composition, from the perspective of weather resistance of the formed coating film, etc.

[0165] [Solvent]

[0166] As the above-mentioned solvent, for example, an organic solvent, water, etc. can be used. As the organic solvent, for example, ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, etc.; ester solvents such as ethyl acetate, butyl acetate, methyl benzoate, ethyl ethoxypropionate, ethyl propionate, methyl propionate, etc.; ether solvents such as tetrahydrofuran, dioxane, dimethoxyethane, etc.; glycol ether solvents such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, 3-methoxybutyl acetate, etc.; aromatic solvents such as toluene, xylene, "Swazol 1000" (manufactured by Cosmo Petroleum Company, trade name, high boiling point petroleum solvent), etc.; aliphatic hydrocarbon solvents such as hexane and heptane.

[0167] The content of the above-mentioned solvent in the coating composition of the present invention is within the range of 0 to 10% by mass based on the total amount of the coating composition. The content of the above-mentioned solvent in the coating composition of the present invention is preferably within the range of 0 to 5% by mass, and more preferably within the range of 0 to 3% by mass, from the perspective of reducing the VOC content in the obtained coating composition and the anti-explosion property of the formed coating film.

[0168] [pigment]

[0169] Examples of the pigment include bright pigments, coloring pigments, extender pigments, etc. These pigments may be used alone or in combination of two or more.

[0170] Examples of the bright pigment include aluminum (including vapor-deposited aluminum), copper, zinc, brass, nickel, glass flakes, aluminum oxide, mica, aluminum oxide coated with titanium oxide and / or iron oxide, and mica coated with titanium oxide and / or iron oxide.

[0171] Examples of the coloring pigments include titanium oxide, zinc oxide, carbon black, molybdenum red, Prussian blue, cobalt blue, azo pigments, phthalocyanine pigments, quinacridone pigments, isoindoline pigments, reduced pigments, perylene pigments, dioxazine pigments, diketopyrrolopyrrole pigments, and heat-insulating pigments.

[0172] Examples of the extender pigment include clay, kaolin, barium sulfate, barium carbonate, calcium carbonate, talc, silica, and alumina white.

[0173] When the coating composition of the present invention contains the above-mentioned pigment, the content of the pigment is preferably in the range of 0.1 to 40% by mass, more preferably in the range of 0.5 to 30% by mass, and even more preferably in the range of 0.7 to 20% by mass, based on the total amount in the coating composition, from the perspective of water-resistant adhesion, hardness and weather resistance of the formed coating film.

[0174] [catalyst]

[0175] As the catalyst, a conventionally known catalyst can be used. Examples of the catalyst include tin octoate, dibutyltin diacetate, dibutyltin di(2-ethylhexanoate), dibutyltin dilaurate, dioctyltin diacetate, dioctyltin di(2-ethylhexanoate), dioctyltin dineodecanoate, dioctyltin diversic acid carbonate, dibutyltin oxide, dibutyltin sulfide, dioctyltin oxide, dibutyltin fatty acid salt, lead 2-ethylhexanoate, zinc octoate, zinc naphthenate, fatty acid zincs, bismuth octoate, bismuth 2-ethylhexanoate, bismuth oleate, bismuth neodecanoate, bismuth versic acid carbonate, bismuth naphthenate, cobalt naphthenate, Calcium octanoate, copper naphthenate, tetra(2-ethylhexyl) titanate, tetrabutyl titanate, diisopropyl bis(acetylacetonate) titanate, tetra(acetylacetonate) titanium, diisopropoxybis(ethyl acetylacetonate)phthalate, butyl titanate dimer, zirconium n-propoxide, zirconium n-butoxide, zirconium tetraacetylacetonate, zirconium tributoxymonoacetylacetonate and other organic metal compounds; triethylamine, N,N'-dimethylcyclohexylamine, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetramethylhexamethylenediamine, N,N,N',N'- ”-pentamethyldiethylenetriamine, N,N,N',N",N"-pentamethyldipropylenetriamine, 1,4-diazabicyclo[2.2.2.]octane (DABCO), 1,8-diazabicyclo[5.4.0.]-7-undecene (DBU), 1,5-diazabicyclo[4.3.0.]-5-nonene (DBN), N-methyl-N'-(2-dimethylaminoethyl)piperazine, N-ethylmorpholine, 1,2-dimethylimidazole, dimethylethanolamine, dimethylaminoethoxyethanol, N-methyl Tertiary amine compounds such as tertiary amine compounds such as 1,2-dimethylaminopropyl-N'-(2-hydroxyethyl)piperazine, 2-hydroxyethyl-1,4-diazabicyclo[2.2.2.]octane, 1,1'-{[3-(dimethylamino)propyl]imino}bis(2-propanol), bis(2-dimethylaminoethyl)ether, bis(2-morpholinoethyl)ether, and neutralized salts of the tertiary amine compounds; quaternary ammonium salts such as carboxylates of tetraalkylammonium, tetraarylammonium and alkylarylammonium, and halides of tetraalkylammonium, tetraarylammonium and alkylarylammonium, which can be used alone or in combination of two or more.

[0176] When the coating composition of the present invention contains the above-mentioned catalyst, the amount of the catalyst compounded is preferably in the range of 0.005 to 2% by mass, more preferably in the range of 0.01 to 1% by mass, based on the total amount of the coating composition, from the perspective of hardness and weather resistance of the formed coating film.

[0177] In addition, when the coating composition of the present invention contains the above-mentioned catalyst, the coating composition of the present invention may contain organic acids such as acetic acid, propionic acid, butyric acid, isovaleric acid, hexanoic acid, 2-ethylbutyric acid, cyclohexane acid, octanoic acid, nonanoic acid, decanoic acid, 2-ethylhexanoic acid, isooctanoic acid, isononanoic acid, lauric acid, palmitic acid, stearic acid, oleic acid, linoleic acid, neodecanoic acid, versatic acid, isobutyric anhydride, itaconic anhydride, acetic anhydride, citraconic anhydride, propionic anhydride, maleic anhydride, butyric anhydride, citric anhydride, trimellitic anhydride, pyromellitic anhydride, and phthalic anhydride; inorganic acids such as hydrochloric acid and phosphoric acid; metal coordination compounds such as acetylacetone and imidazole compounds, etc.

[0178] [Dehydrating agent]

[0179] As the dehydrating agent, conventionally known inorganic dehydrating agents and organic dehydrating agents can be used. Examples of the above-mentioned inorganic dehydrating agent include calcium compounds such as calcium hydride, calcium oxide (quicklime), calcium chloride, and calcium sulfate (gypsum); barium compounds such as barium oxide; magnesium compounds such as magnesium sulfate; sodium compounds such as sodium sulfate and sodium carbonate; copper compounds such as copper sulfate; inorganic silicon compounds such as silica gel; aluminum compounds such as alumina (hydraulic alumina, lithium aluminum hydride, non-crystalline silica alumina, crystalline aluminosilicate (molecular sieve), etc., which can be used alone or in combination of two or more. Examples of the above-mentioned organic dehydrating agent include alkyl orthoformates; alkyl orthoacetates; alkyl orthoborates; vinylsilanes; alkoxysilane compounds; monoisocyanate compounds; aliphatic anhydrides such as acetic anhydride, aromatic anhydrides such as benzoic anhydride, etc., which can be used alone or in combination of two or more.

[0180] When the coating composition of the present invention contains the above-mentioned dehydrating agent, the compounding amount of the dehydrating agent is preferably in the range of 0.1 to 2 mass %, more preferably in the range of 0.3 to 1 mass %, based on the total amount of the coating composition, from the perspective of the anti-pollution property of the formed coating film, etc.

[0181] [Coating film forming method using coating composition]

[0182] The coating composition of the present invention is applied to a substrate to form a wet coating film (uncured coating film), and then the wet coating film is cured to form a target coating film. The substrate is preferably made of a resin material from the viewpoint of water resistance and adhesion of the formed coating film.

[0183] Examples of the resin material include acrylic resins such as polymethyl methacrylate, polyester resins such as polyethylene terephthalate, polyethylene naphthalate, poly-1,4-cyclohexanedimethylene glycol, polyethylene-1,2-diphenoxyethane-4,4'-dicarboxylate, and polybutylene terephthalate; Epoxy resins represented by commercially available products such as epoxy resins (manufactured by Epoxy Co., Ltd.), polycarbonate resins, polyimide resins, novolac resins, phenolic resins, acrylonitrile-butadiene-styrene (ABS) resins, acrylonitrile-ethylene-styrene (AES) resins, acrylonitrile-styrene-acrylate (ASA) resins, vinyl chloride resins, vinylidene chloride resins, polyurethane resins, cellulose ester resins (e.g., cellulose triacetate, cellulose diacetate, cellulose propionate, cellulose butyrate, cellulose acetate propionate, cellulose nitrate), polyamide resins, polystyrene resins (e.g., syndiotactic polystyrene), polyolefin resins (e.g., polypropylene, polyethylene, polymethylpentene), polysulfone resins, polyethersulfone resins, polyarylate resins, polyetherimide resins, polyetherketone resins, various fiber reinforced plastic materials (Fiber Reinforced Plastics: hereinafter sometimes referred to as FRP materials or simply FRP), and polymer alloys thereof.

[0184] Alternatively, the substrate may be coated with a primer, a mid-coat, a top-coat, etc. on the resin material to form a primer, a mid-coat, a top-coat, etc. in advance.

[0185] The substrate may be treated by at least one physical method selected from the group consisting of plasma treatment, corona discharge treatment, active energy ray treatment, flame treatment, sandblasting treatment, grinding treatment and the like (physical treatment).

[0186] It should be noted that the coating composition of the present invention is preferably directly applied on a substrate.

[0187] In addition, there are no particular restrictions on the use of the molded article coated with the coating composition of the present invention, and examples thereof include outer panels of automobile bodies such as cars, trucks, motorcycles, and buses; interior and exterior parts for automobiles such as bumpers, center pillars, rearview mirrors, door handles, instrument panels, door trim, and center consoles; furniture and building material related parts such as chairs, vanity mirrors, window frames, and door panels; outer panels of household electrical products such as mobile phones and audio equipment, etc.

[0188] The method of applying the coating composition of the present invention to the substrate is not particularly limited. For example, the coating composition can be applied by air spraying, airless spraying, rotary atomizing coating machine, dip coating, coater, brush, roller, in-mold coating, etc. During coating, electrostatic application can also be performed.

[0189] The coating film thickness is preferably within a range of 5 to 2000 μm, more preferably within a range of 10 to 1500 μm, and even more preferably within a range of 15 to 1000 μm, as a cured film thickness.

[0190] The coating composition of the present invention can be cured on the applied substrate by heating the coating composition.

[0191] [heating]

[0192] Heating can be performed by any method known in the art. Specifically, for example, hot air, hot gas, infrared heater, IR radiator, oven, hot roller, hot press, microwave, etc. can be used. In the present invention, heating is preferably performed by hot air, infrared heater, hot press, etc. from the aspects of ease of operation.

[0193] From the perspectives of productivity, workability, and thermal stability of the substrate, the heating temperature is preferably in the range of 30 to 200° C., more preferably in the range of 50 to 180° C., and even more preferably in the range of 70 to 160° C. In addition, the heating time is preferably in the range of 20 seconds to 60 minutes, and more preferably in the range of 40 seconds to 10 minutes.

[0194] In addition, the coating composition of the present invention can be suitably used in coating using an in-mold coating method. The in-mold coating method can use a coating composition generally having a low VOC content, thereby reducing air conditioning energy during coating, thereby having the advantage of being able to reduce environmental burden.

[0195] [In-mold coating method]

[0196] The in-mold coating method of the present invention comprises the following steps: injecting the coating composition of the present invention (hereinafter, when the coating composition of the present invention is used in the in-mold coating method, it is referred to as the in-mold coating coating composition) between the molded substrate and the inner wall of the mold, curing the in-mold coating coating composition, and then removing the coated molded object from the mold.

[0197] As the in-mold coating method, the existing method of molding and coating in the mold can be used without particular limitation. Specifically, for example, the method described in Japanese Patent Publication No. 2000-141407 and Japanese Patent Table No. 2008-525212 can be used. It should be noted that the resin molding mold used when molding the resin material and the in-mold coating mold used when coating the in-mold of the in-mold coating coating composition can be the same or different.

[0198] In the case where the above-mentioned resin molding die and the in-mold coating die are the same, for example, a resin material heated and melted in an injection cylinder is injected between the resin molding dies having the shape of a target molded product, cooled and pressurized in the resin molding dies, the resin material is made into a molded product, and then the resin molding dies are separated from the surface of the molded product of the resin material. Next, a gap sufficient to inject the in-mold coating coating composition is set between the surface of the molded product of the resin material and the in-mold coating die, the in-mold coating coating composition is injected between the surface of the molded product of the resin material and the inner wall of the in-mold coating die, the in-mold coating die is closed, and an uncured in-mold coating film is formed on the molded product of the resin material. Next, the uncured in-mold coating film formed on the molded product of the resin material is heated and molded into a target shape, and an in-mold coating molded product having a cured in-mold coating film formed on the molded product of the resin material can be obtained.

[0199] In the case where the above-mentioned resin molding die is different from the first coating film coating die, for example, a resin material heated and melted in an injection cylinder is injected into a resin molding die having the shape of a target molded product, cooled and pressurized in the resin molding die, and the resin material is made into a molded product, and then the resin molding die is separated and disassembled from the surface of the molded product of the resin material. Next, the in-mold coating die is brought close to the surface of the resin molded product, a gap sufficient for injecting the in-mold coating coating composition is set between the surface of the molded product of the resin material and the in-mold coating die, the in-mold coating coating composition is injected between the surface of the molded product of the resin material and the inner wall of the in-mold coating die, and the in-mold coating die is closed to form an uncured in-mold coating film on the molded product of the resin material. Next, the uncured in-mold coating film formed on the molded product of the resin material is heated and molded into a target shape, and an in-mold coating molded product having a cured in-mold coating film formed on the molded product of the resin material can be obtained.

[0200] In addition, from the perspective of the releasability of the in-mold coating molded product from the in-mold coating mold, an external mold release agent may be applied to the mold. As the external mold release agent, for example, fluorine-based, silicone-based, surfactant-based, and wax-based external mold release agents may be used.

[0201] The heating temperature when the molten resin is injected into the cylinder is arbitrarily determined according to the type of resin material, etc., but is preferably 80 to 300° C. The temperature of the mold when injecting the resin material is arbitrarily determined according to the molding time, the type of resin material, etc., but is preferably 30 to 120° C. The molding time of the resin material may be until the resin material is completely solidified, but it can be cured to a strength that does not damage the molded shape when the above-mentioned in-mold coating composition is injected, and is usually preferably about 20 seconds to 60 minutes.

[0202] The amount of the in-mold coating composition injected is an amount sufficient to obtain a desired film thickness, preferably an amount sufficient to obtain a cured film thickness of 15 to 2000 μm.

[0203] The heating temperature when heating the uncured in-mold coating film is preferably in the range of 20 to 160° C., more preferably in the range of 40 to 150° C., and further preferably in the range of 60 to 140° C. In addition, the heating time when heating the uncured in-mold coating film is preferably in the range of 20 seconds to 10 minutes, more preferably in the range of 30 seconds to 5 minutes, and further preferably in the range of 40 seconds to 4 minutes.

[0204] When the uncured in-mold coating film is heated and cured, it is preferably pressurized. In the case of pressurization, the pressure is preferably in the range of 2 to 14 MPa from the viewpoints of water-resistant adhesion and anti-burst properties of the formed coating film.

[0205] Example

[0206] Hereinafter, manufacturing examples, embodiments and comparative examples are listed to further specifically describe the present invention. It should be noted that these manufacturing examples, embodiments and comparative examples are only for illustration and are not intended to limit the scope of the present invention. In manufacturing examples, embodiments and comparative examples, "parts" and "%" are all weight references unless otherwise specified. In addition, the film thickness of the coating film is based on the film thickness of the cured coating film.

[0207] The components used in the following examples are as follows.

[0208] [Production of Carbodiimide Group-Containing Compound (C)]

[0209] [Production Example 1]

[0210] Into a reaction vessel equipped with a thermometer, a thermostat, a dry air introduction pipe, a stirring device and a reflux cooler, 100.0 parts of "CARBODILITE V-05" (trade name, manufactured by Nisshinbo Chemical Co., Ltd., a carbodiimide group-containing compound having an aromatic ring structure and two isocyanate groups, carbodiimide equivalent per solid content of 262, number average molecular weight of 800, solid content concentration of 100%), 0.04 parts of "NEOSTANN U-830" (trade name, manufactured by Nitto Kasei Co., Ltd., dioctyltin ditert-carbonate, solid content concentration of 100%) and 20.0 parts of methanol were charged, and the contents of the reaction vessel were heated to 60° C. while stirring and mixing in a dry air stream. Thereafter, the contents of the reaction vessel were aged for 24 hours, and the disappearance of the isocyanate group was confirmed by IR (infrared absorption) analysis of the reaction product. Next, methanol was distilled off from the contents of the reaction vessel under reduced pressure at 60° C., and the contents of the reaction vessel were cooled to room temperature to obtain a carbodiimide group-containing compound (C-1) having a carbodiimide equivalent per unit solid content of 290, a number average molecular weight of 860, and a solid content concentration of 100%. The obtained carbodiimide group-containing compound has an aromatic ring structure and does not have an isocyanate group.

[0211] [Manufacturing of Pigment Dispersion Liquid (P)]

[0212] [Production Example 2]

[0213] In a container equipped with a stirring device, 4.7 parts of butyl acetate, 1 part of "Raven 5000ULTRA III POWDER" (trade name, manufactured by Birla Carbon, carbon black pigment, solid content concentration 100%), 0.1 part of "SOLSPERSE 5000S" (trade name, manufactured by Lubrisol, phthalocyanine pigment derivative, solid content concentration 100%), and 1 part of "DISPERBYK-2013" (trade name, manufactured by Bick, dispersant, solid content concentration 100%) were added, and the contents of the container were uniformly mixed. Next, the obtained mixed solution and glass beads with a diameter of about 1.3 mmφ as a dispersion medium were placed in a wide-mouthed glass bottle and sealed, and the mixed solution was dispersed for 4 hours using a paint shaker to obtain a pigment dispersion (P-1).

[0214] [Manufacturing of coating composition]

[0215] [Example 1]

[0216] In a container equipped with a stirring device, 34.2 parts of "Desmophen XP2488" (trade name, manufactured by Covestro, a hydroxyl-containing polyester resin containing 26% of a hydroxyl-containing monomer, solid content concentration 100%), 60.4 parts of "Desmodur N3900" (trade name, manufactured by Sumika Covestro Urethane Co., Ltd., iminooxadiazinedione of hexamethylene diisocyanate, solid content concentration 100%), 1.5 parts of "CARBODILITE V-05" (trade name, manufactured by Nisshinbo Chemical Co., Ltd., a carbodiimide group-containing compound having an aromatic ring structure and two isocyanate groups, carbodiimide equivalent per unit solid content 262, number average molecular weight 800, solid content concentration 100%), 0.1 parts of "BYK-333" (trade name, manufactured by BYK, a surface conditioner (polyether-modified polydimethylsiloxane), solid content concentration 100%), and 0.1 parts of "TINUVIN The contents of the container were mixed uniformly to obtain a coating composition No. 1 having a solid content concentration of 99%.

[0217] [Examples 2 to 25 and Comparative Examples 1 to 5]

[0218] In Example 1, coating compositions No. 2 to No. 30 were obtained in the same manner as in Example 1 except that the compounding compositions were as shown in Table 1-1 and Table 1-2 below.

[0219] [Table 1-1]

[0220]

[0221] [Table 1-2]

[0222]

[0223] In addition, each component described in the table is as follows.

[0224] (Note 1) "Desmophen VPLS2249 / 1": trade name, manufactured by Covestro, hydroxyl-containing polyester resin containing 44% of hydroxyl-containing monomer, solid content concentration 100%,

[0225] (Note 2) "Placcel 303": trade name, manufactured by Daicel Corporation, hydroxyl-containing polycaprolactone resin, solid content concentration 100%,

[0226] (Note 3) "Desmophen NH1220": trade name, manufactured by Covestro, N,N'-(2-methylpentane-1,5-diyl)bis-aspartic acid tetraethyl ester, solid content concentration 100%,

[0227] (Note 4) "Desmophen NH1423": trade name, manufactured by Covestro, N,N'-[methylenebis(cyclohexane-4,1-diyl)]bis-aspartic acid tetraethyl ester, solid content concentration 100%,

[0228] (Note 5) "CLEALINK 1000": trade name, manufactured by Dorfketal, N,N'-di-sec-butyl-4,4'-methylenebis(cyclohexylamine), solid content 100%,

[0229] (Note 6) "TMMP-LV": trade name, manufactured by SC Organic Chemicals Co., Ltd., trimethylolpropane tris(3-mercaptopropionate), solid content concentration 100%,

[0230] (Note 7) "TMPIC": trade name, manufactured by SC Organic Chemicals Co., Ltd., tris-[(3-mercaptopropionyloxy)-ethyl]isocyanurate, solid content concentration 100%,

[0231] (Note 8) "PEMP-LV": trade name, manufactured by SC Organic Chemical Co., Ltd., pentaerythritol tetrakis (3-mercaptopropionate), solid content concentration 100%,

[0232] (Note 9) "Desmodur N3400": Trade name, manufactured by Sumika Covestro Urethane Co., Ltd., mixture of uretdione of hexamethylene diisocyanate and isocyanurate, solid content 100%,

[0233] (Note 10) "Desmodur NZ200": trade name, manufactured by Sumika Covestro Urethane Co., Ltd., a mixture of isocyanurate of hexamethylene diisocyanate and isocyanurate of isophorone diisocyanate, solid content concentration 100%,

[0234] (Note 11) "Desmodur N3600": trade name, manufactured by Sumika Covestro Urethane Co., Ltd., isocyanurate of hexamethylene diisocyanate, solid content 100%,

[0235] (Note 12) "CARBODILITE V-03": manufactured by Nisshinbo Chemical Co., Ltd., a carbodiimide group-containing compound having no aromatic ring structure and no isocyanate group, carbodiimide equivalent per unit solid content 216, number average molecular weight 2000, solid content concentration 50%,

[0236] (Note 13) “CARBODILITE V-09M”: manufactured by Nisshinbo Chemical Co., Ltd., a carbodiimide group-containing compound having an aromatic ring structure and no isocyanate group, carbodiimide equivalent per unit solid content of 200, number average molecular weight of 15,000, solid content concentration of 70%.

[0237] [Preparation of test coated plate (T1)]

[0238] [Example 26]

[0239] First, "DIALAC TW20" (trade name, manufactured by Techno-UMG, acrylonitrile-styrene-acrylate resin (ASA resin)) was filled into the injection molding cylinder, and the "DIALAC TW20" was heated and melted at 230°C. Then, the heated and melted "DIALAC TW20" was injected into the mold at 60°C, and the pressure was maintained for 30 seconds, and the "DIALAC TW20" was cooled. Next, the solidified "DIALAC TW20" was taken out of the mold to obtain a flat plate-shaped "DIALAC TW20" substrate of 100 mm×100 mm×2 mm. Next, the surface of the flat plate-shaped "DIALAC TW20" substrate was degreased with isopropyl alcohol, and then the coating composition No. 1 obtained in Example 1 was applied to the surface of the flat plate-shaped "DIALAC TW20" substrate using an applicator so that the cured film thickness was 100 μm to form a coating film, and the coating film was immediately heated at 80° C. for 3 minutes to cure, thereby preparing a test coated plate (T1-1).

[0240] [Preparation of test coated panels (T2)]

[0241] First, "Makroblend UT235M" (trade name, manufactured by Covestro, a polymer alloy of polyethylene terephthalate resin and polycarbonate resin) was filled into the injection molding barrel, and the "Makroblend UT235M" was heated and melted at 270°C. Then, the heated and melted "Makroblend UT235M" was injected into the mold at 70°C, and the pressure was maintained for 30 seconds, and the "Makroblend UT235M" was cooled. Next, the solidified "Makroblend UT235M" was removed from the mold to obtain a flat "Makroblend UT235M" substrate of 100 mm × 100 mm × 2 mm. Next, the surface of the flat-plate "Makroblend UT235M" substrate was degreased with isopropyl alcohol, and then the coating composition No. 1 obtained in Example 1 was applied to the surface of the flat-plate "Makroblend UT235M" substrate using an applicator in a manner such that the cured film thickness was 100 μm to form a coating film, and the coating film was immediately heated at 80° C. for 3 minutes to cure it, thereby preparing a test coated plate (T2-1).

[0242] [Examples 27 to 50 and Comparative Examples 6 to 10]

[0243] In Example 26, except that the types of coating compositions were as shown in Tables 2-1 and 2-2 below, test coated plates (T1-2) to (T1-30) and (T2-2) to (T2-30) were prepared in the same manner as in Example 26.

[0244] The obtained test coated panels were evaluated for water-resistant adhesion, hardness, and weather resistance. The evaluation results are shown in Tables 2-1 and 2-2.

[0245] [Water-resistant adhesion]

[0246] Each test coated plate obtained in Examples 26 to 50 and Comparative Examples 6 to 10 was immersed in warm water at 40°C for 240 hours and then pulled up, and each test coated plate was dried at 20°C for 24 hours. Next, the coating film of each test coated plate after the water resistance test was cut into a grid shape with a cutter in such a way as to reach the base, and 100 checkerboards of 2 mm × 2 mm in size were made. Next, an adhesive cellophane tape was pasted on the surface of each test coated plate with a cut, and the adhesive cellophane tape was peeled off sharply at a temperature of 23 ± 2°C and a relative humidity of 50 ± 5% RH. The remaining state of the checkerboard coating film after peeling was investigated, and the adhesion after the water resistance test was evaluated based on the following criteria. A, B and C were qualified.

[0247] A: 100 checkered-grid coating films remain, and no small edge chipping or lifting of the coating film occurs at the edges of the cuts made by the cutter.

[0248] B: 100 checkered patterns of the coating film remain, and small edge chips or lifting of the coating film occur at the edges of the cuts made by the cutter.

[0249] C: 90 to 99 checkerboard coatings remain.

[0250] D: 80 to 89 checkerboard coatings remain.

[0251] E: The number of remaining cross-section coating films was 79 or less.

[0252] [hardness]

[0253] The martensitic hardness (N / mm) of each of the test coated plates obtained in Examples 26 to 50 and Comparative Examples 6 to 10 was measured using "FISCHERSCOPE (registered trademark) HM2000S" (trade name, manufactured by FISCHER INSTRUMENTS). 2 ), and the evaluation was conducted based on the following criteria. The measurement conditions were: indenter: quadrangular pyramid Vickers indenter (material: diamond, opposite angle: 136°), maximum test load: 20 mN, indentation speed: 20 mN / 25 seconds, temperature: 21±2°C, relative humidity: 50±5%RH. A, B, and C were qualified.

[0254] A: Martensite hardness is 125N / mm 2 above.

[0255] B: Martensite hardness is 100N / mm 2 Above and less than 125N / mm 2 .

[0256] C: Martensite hardness is 75N / mm 2 Above and less than 100N / mm 2 .

[0257] D: Martensite hardness is 50N / mm 2 Above and less than 75N / mm 2 .

[0258] E: Martensite hardness is less than 50N / mm 2 .

[0259] [Weather resistance]

[0260] The test coated plates obtained in Examples 26 to 50 and Comparative Examples 6 to 10 were irradiated with light at angles of 25°, 45°, and 75° relative to the axis perpendicular to the coating surface using a multi-angle spectrophotometer "CM-512m3" (manufactured by Konica Minolta). The light in the direction perpendicular to the coating surface among the reflected light was measured by L * 、a* 、b * Color measurement was performed. Next, based on JIS K 5600-7-7 (2008), an accelerated weather resistance test was performed using a "Super Xenon Weather Meter" (manufactured by Suga Test Instruments, a weather resistance tester) under the conditions of a test piece wetting cycle of 18 minutes / 2 hours, a blackboard temperature of 61 to 65°C, and a lamp irradiation time of 1,200 hours. Next, for each test coated plate after the accelerated weather resistance test, the multi-angle spectrophotometer "CM-512m3" (manufactured by Konica Minolta) was used to irradiate light at angles of 25°, 45°, and 75° relative to the axis perpendicular to the coating surface, and the light in the direction perpendicular to the coating surface among the reflected light was measured by L * 、a * 、b * Next, the L before and after the accelerated weathering test were * 、a * 、b * Colorimetric values, ΔE at 25°, 45° and 75° calculated according to JIS K 5600-4-6 (1999) * (25°), ΔE * (45°) and ΔE * (75°), ΔE based on the following criteria * (25°), ΔE * (45°) and ΔE * (75°) The largest ΔE * Evaluation was performed. ΔE * The smaller the value, the smaller the discoloration of the test plate, indicating better weather resistance. A, B and C are qualified.

[0261] A: ΔE * Less than 1.0.

[0262] B: ΔE * It is 1.0 or more and less than 1.5.

[0263] C: ΔE * It is 1.5 or more and less than 2.0.

[0264] D: ΔE * It is 2.0 or more and less than 3.0.

[0265] E: ΔE * 3.0 or above.

[0266] [Table 2-1]

[0267]

[0268] [Table 2-2]

[0269]

[0270] [Manufacturing of in-mold coating composition]

[0271] Embodiment 51

[0272] In a container equipped with a stirring device, 33.9 parts of "Desmophen XP2488" (trade name, manufactured by Covestro, a hydroxyl-containing polyester resin containing 26% of a hydroxyl-containing monomer, solid content concentration 100%), 60.1 parts of "Desmodur N3900" (trade name, manufactured by Sumika Covestro Urethane Co., Ltd., iminooxadiazinedione of hexamethylene diisocyanate, solid content concentration 100%), 1.5 parts of "CARBODILITE V-05" (trade name, manufactured by Nisshinbo Chemical Co., Ltd., a carbodiimide group-containing compound having an aromatic ring structure and two isocyanate groups, carbodiimide equivalent per unit solid content 262, number average molecular weight 800, solid content concentration 100%), and 1.5 parts of "Moldwiz The contents of the container were mixed uniformly with 0.6 parts of "INT-120IMC" (trade name, manufactured by AXELPLASTICS, a mixture containing tertiary dimethyl amide of fatty acid, solid content concentration 100%), 0.1 parts of "BYK-333" (trade name, manufactured by BYK, a surface conditioner (polyether-modified polydimethylsiloxane), solid content concentration 100%), 1.2 parts of "TINUVIN 400" (trade name, manufactured by BASF, a triazine-based ultraviolet absorber, solid content concentration 85%), 2.0 parts of "TINUVIN 292" (trade name, manufactured by BASF, a light stabilizer of a hindered amine compound, solid content concentration 100%), and 0.6 parts of "NEOSTANN U-830" (trade name, manufactured by Nitto Kasei Co., Ltd., dioctyltin ditert-carbonate, solid content concentration 100%), to obtain an in-mold coating composition No. 1 having a solid content concentration of 99%.

[0273] [Examples 52 to 85 and Comparative Examples 11 to 15]

[0274] In Example 51, in-mold coating compositions No. 2 to No. 40 were obtained in the same manner as in Example 51 except that the compounding compositions were as shown in Table 3-1 and Table 3-2 below.

[0275] [Evaluation of in-mold coating composition]

[0276] The transparency of the obtained in-mold coating composition was evaluated. The evaluation results are shown in Table 3-1 and Table 3-2.

[0277] [Transparency]

[0278] On a transparent glass plate whose total light transmittance was previously measured using a "color and turbidity simultaneous measuring device COH 400" (trade name, manufactured by Nippon Denshoku Industries, haze meter), the in-mold coating composition obtained in Examples 51 to 85 and Comparative Examples 11 to 15 was applied using an applicator in a manner such that the cured film thickness was 210±20 μm to form a coating film, which was immediately heated and cured at 80°C for 3 minutes to obtain a coated plate for a transparency test. The total light transmittance of the obtained coated plate for a transparency test was measured using a "color and turbidity simultaneous measuring device COH400" (trade name, manufactured by Nippon Denshoku Industries, haze meter), and the total light transmittance of the transparent glass plate was subtracted from the total light transmittance of the transparent test coated plate, and the total light transmittance of the coating film was evaluated based on the following criteria. A, B, and C were qualified.

[0279] A: The total light transmittance is 90% or more.

[0280] B: The total light transmittance is 88% or more and less than 90%.

[0281] C: The total light transmittance is 86% or more and less than 88%.

[0282] D: The total light transmittance is 84% ​​or more and less than 86%.

[0283] E: The total light transmittance is less than 84%.

[0284] [Table 3-1]

[0285]

[0286] [Table 3-2]

[0287]

[0288] In addition, each component described in the table is as follows.

[0289] (Note 14) "AMIDE AP-1": Trade name, manufactured by Mitsubishi Chemical Corporation, stearamide, solid content concentration 100%,

[0290] (Note 15) "NEUTRON PNT-34": trade name, manufactured by Nippon Seika Co., Ltd., N-oleyl palmitamide, solid content concentration 100%,

[0291] (Note 16) "Methyl Stearate 95": Trade name, manufactured by NOF Corporation, methyl stearate, solid content concentration 100%,

[0292] (Note 17) "DAIFREE FB-962": Trade name, manufactured by Daikin Corporation, fluorine-based polymer, solid content concentration 100%,

[0293] (Note 18) “NEWPOL 50HB-5100”: trade name, manufactured by Sanyo Chemical Co., Ltd., polyoxyalkylene ether oligomer, solid content concentration 100%.

[0294] [Production of in-mold overmolded article (M1)]

[0295] [Example 86]

[0296] First, "DIALAC TW20" (trade name, manufactured by Techno-UMG, acrylonitrile-styrene-acrylate resin (ASA resin)) was filled into the injection molding barrel, and the "DIALAC TW20" was heated and melted at 230°C. Thereafter, the heated and melted "DIALAC TW20" was injected between the resin molding dies at 60°C, and the pressure was maintained for 30 seconds, and the "DIALAC TW20" was cooled. Next, the solidified "DIALAC TW20" was taken out of the mold to obtain a flat plate-shaped "DIALACTW20" molded product of 100 mm × 100 mm × 2 mm. Next, the resin molding mold was temporarily opened, and the in-mold coating composition No. 1 obtained in Example 51 was injected between the obtained flat plate-shaped "DIALAC TW20" molded product and the coating film-coated mold. The coating film coated mold was heated to 80°C and maintained at this temperature. After the molding pressure was applied at 5 MPa for 1 minute, the pressure was reduced and the coating film coated mold was opened. Thus, an in-mold coated product (M1-1) was produced in which a flat plate-shaped "DIALAC TW20" molded product was coated with a coating film with a cured film thickness of 200 μm.

[0297] [Production of in-mold overmolded article (M2)]

[0298] First, fill the injection molding barrel with "Makroblend UT235M" (trade name, manufactured by Covestro, a polymer alloy of polyethylene terephthalate resin and polycarbonate resin), and heat and melt the "Makroblend UT235M" at 270°C. Then, inject the heated and melted "Makroblend UT235M" between the resin molding dies at 70°C, maintain the pressure for 30 seconds, and cool the "Makroblend UT235M". Next, take the solidified "Makroblend UT235M" out of the mold to obtain a 100mm×100mm×2mm flat-plate "Makroblend UT235M" molded product. Next, temporarily punch the resin molding mold, and inject the in-mold coating composition No. 1 obtained in Example 51 between the obtained flat-plate "Makroblend UT235M" molded product and the coating film-coated mold. The coating-coated mold was heated to 80°C and maintained at that temperature, then pressurized at a molding pressure of 5 MPa for 1 minute, and then decompressed and the coating-coated mold was opened, thereby producing an in-mold coated product (M2-1) in which a coating with a cured film thickness of 200 μm was coated on a flat-plate "Makroblend UT235M" molded product.

[0299] [Examples 87 to 120 and Comparative Examples 16 to 20]

[0300] In Example 86, in-mold molded products (M1-2) to (M1-40) and (M2-2) to (M2-40) were produced in the same manner as in Example 86 except that the types of coating compositions were as shown in Tables 4-1 and 4-2 below.

[0301] [Evaluation of In-Mold Overmolded Articles]

[0302] The cured coating films on the obtained in-mold overmolded products were evaluated for water-resistant adhesion, hardness, weather resistance, anti-blasting and mold release properties. The evaluation results are shown in Tables 4-1 and 4-2.

[0303] [Water-resistant adhesion]

[0304] Each in-mold coated article obtained in Examples 86 to 120 and Comparative Examples 16 to 20 was immersed in warm water at 40°C for 240 hours and then pulled up, and each in-mold coated article was dried at 20°C for 24 hours. Next, the coating film of each in-mold coated article after the water resistance test was cut into a grid shape with a cutter in a manner that reaches the substrate, and 100 checkerboards of 2 mm × 2 mm in size were made. Next, an adhesive cellophane tape was pasted on the surface of each test coated plate with a cutout, and the adhesive cellophane tape was rapidly peeled off at a temperature of 23±2°C and a relative humidity of 50±5%RH. The remaining state of the checkerboard coating film after peeling was investigated, and the adhesion after the water resistance test was evaluated based on the following criteria. A, B and C were qualified.

[0305] A: 100 checkered-grid coating films remain, and no small edge chipping or lifting of the coating film occurs at the edges of the cuts made by the cutter.

[0306] B: 100 checkered patterns of the coating film remain, and small edge chips or lifting of the coating film occur at the edges of the cuts made by the cutter.

[0307] C: 90 to 99 checkerboard coatings remain.

[0308] D: 80 to 89 checkerboard coatings remain.

[0309] E: The number of remaining cross-section coating films was 79 or less.

[0310] [hardness]

[0311] The martensitic hardness (N / mm) of the cured coating films on the in-mold molded products obtained in Examples 86 to 120 and Comparative Examples 16 to 20 was measured using "FISCHERSCOPE (registered trademark) HM2000S" (trade name, manufactured by FISCHERINSTRUMENTS CO., LTD.). 2 ), and the evaluation was conducted based on the following criteria. The measurement conditions were: indenter: quadrangular pyramid Vickers indenter (material: diamond, opposite angle: 136°), maximum test load: 20 mN, indentation speed: 20 mN / 25 seconds, temperature: 21±2°C, relative humidity: 50±5%RH. A, B, and C were qualified.

[0312] A: Martensite hardness is 125N / mm 2 above.

[0313] B: Martensite hardness is 100N / mm 2 Above and less than 125N / mm 2 .

[0314] C: Martensite hardness is 75N / mm 2 Above and less than 100N / mm 2 .

[0315] D: Martensite hardness is 50N / mm 2 Above and less than 75N / mm 2 .

[0316] E: Martensite hardness is less than 50N / mm 2 .

[0317] [Weather resistance]

[0318] The in-mold coated articles obtained in Examples 86 to 120 and Comparative Examples 16 to 20 were irradiated with light at angles of 25°, 45°, and 75° relative to the axis perpendicular to the coating surface using a multi-angle spectrophotometer "CM-512m3" (manufactured by Konica Minolta Co., Ltd.), and the light in the direction perpendicular to the coating surface among the reflected light was measured by L * 、a * 、b * Color measurement was performed. Next, based on JIS K 5600-7-7 (2008), an accelerated weather resistance test was performed using a "Super Xenon Weather Meter" (manufactured by Suga Test Instruments, weather resistance tester) under the conditions of test piece wetting cycle: 18 minutes / 2 hours, blackboard temperature: 61-65°C, and lamp irradiation time: 1,200 hours. Next, for each in-mold coated molded product after the accelerated weather resistance test, the multi-angle spectrophotometer "CM-512m3" (manufactured by Konica Minolta) was used to irradiate light at angles of 25°, 45°, and 75° relative to the axis perpendicular to the coating surface, and the light in the direction perpendicular to the coating surface among the reflected light was measured by L * 、a * 、b * Next, the L before and after the accelerated weathering test were * 、a * 、b * Colorimetric values, ΔE at 25°, 45° and 75° calculated according to JIS K 5600-4-6 (1999) * (25°), ΔE * (45°) and ΔE * (75°), ΔE based on the following criteria * (25°), ΔE * (45°) and ΔE * (75°) The largest ΔE * Evaluation was performed. ΔE * The smaller the value, the less discoloration of the coating film, indicating better weather resistance.

[0319] A, B and C are qualified.

[0320] A: ΔE * Less than 1.0.

[0321] B: ΔE * It is 1.0 or more and less than 1.5.

[0322] C: ΔE * It is 1.5 or more and less than 2.0.

[0323] D: ΔE * It is 2.0 or more and less than 3.0.

[0324] E: ΔE * 3.0 or above.

[0325] [Blast resistance]

[0326] The in-mold molded articles obtained in Examples 86 to 120 and Comparative Examples 16 to 20 were visually observed, and the number of cracks generated on the coating film surface of the in-mold molded articles was counted, and the crack resistance was evaluated according to the following criteria. A, B, and C were acceptable.

[0327] A: There are no holes larger than 1 mm on the molded product, and there are no more than 3 holes smaller than 1 mm.

[0328] B: There are no holes larger than 1 mm on the molded product, and there are 4 to 6 holes smaller than 1 mm.

[0329] C: There are no holes larger than 1 mm on the in-mold overmolded product, and there are 7 or more holes smaller than 1 mm.

[0330] D: There are 1 to 3 holes larger than 1 mm in size on the molded product.

[0331] E: There are 4 or more blast holes with a size of 1 mm or more on the in-mold overmolded article.

[0332] [Mold release]

[0333] In the production of the above-mentioned in-mold coated molded products (M1) and (M2), when releasing the film-coated mold, a scraper was inserted into the gap between one of the four corners of the in-mold coated mold and the film-coated mold and lifted to make the in-mold coated mold demolded from the film-coated mold. In the case where the in-mold coated composition cannot be demolded, the scraper was pulled out, and the scraper was inserted into the gap between one of the four corners adjacent to the right and the film-coated mold again, and the demolding test was performed in the same way. The demolding test was performed at all four corners until the in-mold coated composition was demolded, and a total of 4 times was implemented at most. In addition, for the in-mold coated molded products where the peeling of the coating was observed, the surface of the in-mold coated molded products was observed with the naked eye, the number of peeling of the coating was counted, and the demolding property was evaluated according to the following benchmarks. A, B, and C were qualified.

[0334] A: In the first and second mold release tests, the in-mold overmolded article was released from the mold, and the number of peeled coating films was 0.

[0335] B: In the 3rd to 4th demolding test, the in-mold overmolded product was released from the mold, and the number of peeled coating films was 0.

[0336] C: In the first to fourth release tests, the in-mold overmolded product was released from the mold, and the number of peeled coating films was 1.

[0337] D: In the first to fourth release tests, the in-mold coated product was released from the mold, and the number of peeled coating films was 2 or more.

[0338] E: Even after the mold release test was performed 4 times, the in-mold overmolded article was not released from the mold, or the coating film was completely peeled off from the substrate.

[0339] [Table 4-1]

[0340]

[0341] [Table 4-2]

[0342]

Claims

1. A coating composition, characterized in that The coating composition comprises (A) an isocyanate-reactive group-containing compound, (B) a polyisocyanate compound, and (C) a carbodiimide group-containing compound, wherein the solid content concentration of the coating composition is 90% by mass or more.

2. The coating composition according to claim 1, wherein The carbodiimide group-containing compound (C) has an isocyanate group.

3. The coating composition according to claim 1 or 2, wherein The carbodiimide group-containing compound (C) has an aromatic ring structure.

4. The coating composition according to any one of claims 1 to 3, wherein The number average molecular weight of the carbodiimide group-containing compound (C) is in the range of 500 to 5,000.

5. An in-mold coating method, comprising the steps of: injecting an in-mold coating composition between a molded substrate and an inner wall of a mold, curing the in-mold coating composition, and then removing the coated molded object from the mold, wherein: The in-mold coating composition is the coating composition according to any one of claims 1 to 4.

6. The in-mold coating method according to claim 5, wherein: The in-mold coating composition further comprises an internal mold release agent (D).

7. The in-mold coating method according to claim 6, wherein: The internal mold release agent (D) comprises fatty amide.

Citation Information

Patent Citations

  • Method for coating in mold

    JP2000141407A

  • Methods of molding and coating substrates

    JP2008525212A

  • Two-component coating material composition for coating fiber-reinforced plastic materials - Patents.com

    JP2020528103A

  • Curable coating composition, laminated polyester resin film and solar cell back sheet

    JP2013216777A

  • Processes for in-mold coating of polymer substrates

    US20200061875A1

Cited By

  • Anti-aging polyether-ether-ketone composite material and production method thereof

    CN121379097A